Electrochemical cell with high viscosity semi-solid electrode and method of making same
Through the combination of high viscosity semi-solid electrodes and high salt concentration electrolytes, the problem of lithium ion loss and ion transmission limitations during fast charging and discharge of electrochemical cell units is solved, achieving higher rate performance and charging capacity.
Patent Information
- Application Number
- CN202380040381.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-21
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-27
AI Technical Summary
The existing electrochemical cell has severe lithium ion loss during fast charging and discharge, and the ion transmission of thick electrodes is limited, affecting the battery's rate performance.
Using a high viscosity semi-solid electrode method, by combining the active material with conductive material and high concentration of non-aqueous liquid electrolyte, a semi-solid cathode with a thickness of up to 150μm or more is formed, and a high salt concentration electrolyte is used in the electrochemical cell to promote Ion transport, combining carbon coating and density gradients to improve contact and conductivity of the electrodes.
The rate performance and charging capacity of the electrochemical cell are significantly improved, the use of inactive materials of the electrodes is reduced, the cost is reduced, and the energy density is increased.
Smart Images

Figure CN119213575A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 354,056, filed on June 21, 2022, and entitled “Electrochemical Cells with High-Viscosity Semi-Solid Electrodes, and Methods of Making the Same,” the disclosure of which is hereby incorporated by reference in its entirety. Technical Field
[0003] Embodiments described herein relate to high viscosity semi-solid electrodes and methods of making the same. Background Art
[0004] When producing an electrochemical cell, the electrode can be coated onto a current collector and the electrolyte can be added afterwards. The coating of the current collector and the addition of the electrolyte are usually separate steps. This manufacturing process may limit the feasible thickness of the electrode and the choice of electrolyte. Semi-solid electrodes can be made with active materials, conductive materials, and electrolytes. The active materials, conductive materials, and electrolytes can be cast together into a semi-solid electrode. Semi-solid electrodes can be manufactured without the use of binders, making the movement of electroactive materials less restricted. However, thick semi-solid electrodes are often constrained by ion transport limitations. Lithium ion loss during charging or discharging can be a problem, especially during rapid charging and rapid discharging. Improving ion transport can alleviate these problems. Summary of the invention
[0005] Embodiments described herein relate to methods of producing a semi-solid electrode. In some aspects, a method may include: combining an active material with a conductive material and a non-aqueous liquid electrolyte to form a semi-solid cathode, wherein the salt concentration of the non-aqueous liquid electrolyte is at least about 2,000 mol / m 3; placing the semi-solid cathode on a cathode current collector, the thickness of the semi-solid cathode being at least about 150 μm; placing the anode on the anode current collector; wetting the first surface of the separator with the non-aqueous liquid electrolyte; coating the first surface of the separator with a carbon coating; and placing the anode on the cathode with the separator inserted therebetween to form an electrochemical cell, such that the first surface of the separator is in contact with the semi-solid cathode. In some embodiments, the method may further include charging and discharging the electrochemical cell while orienting the electrochemical cell so that the thickness of the cathode is aligned with the direction of gravity. In some embodiments, the salt concentration of the non-aqueous liquid electrolyte may be at least about 3,000 mol / m 3 In some embodiments, the carbon coating may include hard carbon. In some embodiments, the rate of the discharge is at least about 1.5C. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 is a block diagram of a method for producing a high viscosity semi-solid electrode according to an embodiment.
[0007] Figure 2 is a block diagram of an electrochemical cell having a high viscosity semi-solid electrode according to an embodiment.
[0008] Figure 3 is a schematic diagram of an electrochemical cell having a high viscosity semi-solid electrode according to an embodiment.
[0009] Figure 4A-4B The simulated potential and electrolyte salt concentration of a high viscosity semi-solid electrode according to an embodiment are shown.
[0010] Figure 5 The density of the semi-solid electrode is shown as a function of the electrolyte salt concentration.
[0011] Figure 6 The rate performance is shown for different battery cell orientations.
[0012] Figure 7 The capacity retention and internal resistance of the battery cell at different orientations are shown.
[0013] Figure 8 The capacity retention of an electrochemical cell with a high viscosity semi-solid electrode is shown.
[0014] Fig. 9 The capacity retention of an electrochemical cell with a high viscosity semi-solid electrode is shown. DETAILED DESCRIPTION
[0015] Embodiments described herein relate to high viscosity semi-solid electrodes and methods for making the same. The semi-solid electrodes described herein can be made: (i) thicker (e.g., greater than 100 μm to up to 2,000 μm or even greater) due to the reduced tortuosity and higher conductivity of the semi-solid electrodes, (ii) with higher active material loading, and (iii) with a simplified manufacturing process using less equipment. These relatively thick semi-solid electrodes reduce the volume, mass, and cost contribution of inactive components relative to active components, thereby enhancing the commercial appeal of batteries made from semi-solid electrodes. In some embodiments, the semi-solid electrodes described herein are binder-free and / or do not use binders used in conventional battery manufacturing. Instead, the electrode volume typically occupied by binders in conventional electrodes is now occupied by: 1) electrolytes, which have the effect of reducing tortuosity and increasing the total salt available for ion diffusion, thereby offsetting the typical salt loss effects of thick conventional electrodes when used at high rates, 2) active materials, which have the effect of increasing the charge capacity of the battery, or 3) conductive additives, which have the effect of increasing the conductivity of the electrode, thereby offsetting the high internal resistance of thick conventional electrodes. The reduced tortuosity and higher conductivity of the semi-solid electrodes described herein produce excellent rate performance and charge capacity of electrochemical cells formed by semi-solid electrodes. Since the semi-solid electrodes described herein can be made much thicker than conventional electrodes, the ratio of active materials (i.e., semi-solid cathodes and / or anodes) to inactive materials (i.e., current collectors and separators) in a battery formed by an electrochemical cell stack including semi-solid electrodes may be much higher relative to a similar battery formed by an electrochemical cell stack including conventional electrodes. This significantly increases the total charge capacity and energy density of batteries including the semi-solid electrodes described herein.
[0016] In some embodiments, the electrode material described herein may be a flowable semi-solid or condensed liquid composition. In some embodiments, the electrode material described herein may be binder-free or substantially free of binder. A flowable semi-solid electrode may include a suspension of an electrochemically active material (anode or cathode particles or microparticles) and an optional conductive material (e.g., carbon) in a non-aqueous liquid electrolyte. In other words, active electrode particles and conductive particles are co-suspended in an electrolyte to produce a semi-solid electrode. An example of a battery architecture utilizing a semi-solid suspension is described in International Patent Publication No. WO 2012 / 024499 entitled "Stationary, Fluid Redox Electrode" and International Patent Publication No. WO 2012 / 088442 entitled "Semi-Solid Filled Battery and Method of Manufacture", the entire disclosure of which is hereby incorporated by reference.
[0017] The power of thick electrodes is generally limited by ion transport. Lithium ion loss during charging or discharging is an important issue in battery cells, especially during fast charging (e.g., at least 1C) or fast discharging (e.g., at least 1C). High concentrations of electrolyte salts can alleviate lithium ion loss. However, long ion transport paths in thick electrodes may limit the rate performance of electrochemical cells using thick semi-solid electrodes. In terms of rate performance, ion transport has historically been considered to be dominated by migration and diffusion. Migration is ion transport driven by a voltage gradient. Diffusion is the transport of ions and species driven by a concentration gradient.
[0018] In some cases, lithium ion transport and power output of battery cells with semi-solid electrodes can be achieved by convection or bulk transport driven by density gradient. Convection can be introduced into thick semi-solid electrodes using electrolytes with high salt concentrations. During charging or discharging, thick electrodes with highly concentrated electrolytes produce significant electrolyte concentration gradients throughout the electrochemical cell. This allows the introduction of significant density gradients and the resulting effective convection transport. The introduction of electrolytes with high salt concentrations can increase the viscosity of the semi-solid electrode and the electrolyte therein, as well as ion transport within the semi-solid electrode.
[0019] However, the wettability of semi-solid electrodes may be limited. In other words, high viscosity semi-solid electrodes may have problems contacting the separator and / or current collector. Wetting the separator with an electrolyte solution can facilitate this contact. Coating the separator and / or current collector with a carbonaceous material can also facilitate contact and ion movement.
[0020] Cells with semi-solid electrodes and concentrated electrolytes have shown enhanced rate performance. Gravity and density gradients can be used to induce convective bulk transport. The density of the electrolyte can be caused by temperature differences, the structure of the electrode materials, and / or electrolyte additives. The driving force for bulk transport is not limited to gravity. In some embodiments, bulk transport can be achieved by applying a magnetic field, a temperature gradient, and / or a centrifugal force.
[0021] As used in this specification, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, the term "member" is intended to mean a single member or a combination of members, and "material" is intended to mean one or more materials or a combination thereof.
[0022] When used in conjunction with "cylindrical," "linear," and / or other geometric relationships, the term "substantially" is intended to convey that the structure so defined is nominally cylindrical, linear, etc. As an example, a portion of a support member described as "substantially linear" is intended to convey that while linearity of the portion is desired, some nonlinearity may occur in the "substantially linear" portion. Such nonlinearity may result from manufacturing tolerances or other practical considerations (such as pressure or forces applied to the support member). Thus, a geometric structure modified by the term "substantially" includes such geometric properties within a tolerance range of plus or minus 5% of the geometric structure. For example, a "substantially linear" portion is a portion that defines an axis or centerline whose linearity error is within plus or minus 5%.
[0023] As used herein, the terms "group" and "plurality" may refer to multiple features or a single feature having multiple parts. For example, when referring to a group of electrodes, the group of electrodes may be considered to be one electrode having multiple parts, or the group of electrodes may be considered to be multiple different electrodes. In addition, for example, when referring to multiple electrochemical cells, the multiple electrochemical cells may be considered to be multiple different electrochemical cells or to be one electrochemical cell having multiple parts. Thus, a group of parts or multiple parts may include multiple parts that are continuous or discontinuous with each other. Multiple particles or multiple materials may also be made from multiple items that are produced separately and subsequently joined together (e.g., by mixing, adhesives, or any suitable method).
[0024] As used herein, the term "semi-solid" refers to a material that is a mixture of a liquid phase and a solid phase, such as a particle suspension, a slurry, a colloidal suspension, an emulsion, a gel, or a micelle.
[0025] As used herein, the terms "activated carbon network" and "networked carbon" refer to the general qualitative state of an electrode. For example, an electrode having an activated carbon network (or networked carbon) causes the carbon particles within the electrode to present individual particle morphology and arrangement relative to each other, which promotes electrical contact and conductivity between particles and across the thickness and length of the electrode. In contrast, the terms "unactivated carbon network" and "unnetworked carbon" refer to electrodes in which carbon particles exist as individual particle islands or multi-particle aggregate islands, which may not be sufficiently connected to provide sufficient electrical conduction through the electrode.
[0026] As used herein, the terms "energy density" and "volume energy density" refer to the amount of energy (e.g., MJ) stored in an electrochemical cell per unit volume (e.g., L) of materials (e.g., electrodes, separators, electrolytes, and current collectors) included for the operation of the electrochemical cell. Specifically, the materials used to package the electrochemical cell are excluded from the calculation of volumetric energy density.
[0027] As used herein, the term "high capacity material" or "high capacity anode material" refers to a material with an irreversible capacity greater than 300 mAh / g, which can be incorporated into an electrode to promote the absorption of electroactive species. Examples include tin, tin alloys such as Sn-Fe, tin oxide, silicon, silicon alloys such as Si-Co, silicon oxide, aluminum, aluminum alloys, metal oxides (CoO, FeO, etc.) or titanium oxide.
[0028] As used herein, the term "composite high capacity electrode layer" refers to an electrode layer having both a high capacity material and a traditional anode material (eg, a silicon-graphite layer).
[0029] As used herein, the term "solid high-capacity electrode layer" refers to an electrode layer having a single solid phase high-capacity material, such as sputtered silicon, tin, tin alloys such as Sn-Fe, tin oxide, silicon, silicon alloys such as Si-Co, silicon monoxide, aluminum, aluminum alloys, metal oxides (CoO, FeO, etc.) or titanium oxide.
[0030] As used herein, "density gradient" refers to a spatial variation in density at different depths. In other words, the amount of a substance per unit volume changes from a first location to a second location.
[0031] Figure 1is a block diagram of a method 10 for producing a high viscosity semi-solid electrode according to an embodiment. As shown, the method 10 includes combining an active material with a conductive material and a non-aqueous liquid electrolyte to form a semi-solid electrode at step 11, and placing the semi-solid electrode on a first current collector at step 12. The method 10 optionally includes placing a second electrode on a second current collector at step 13. The method 10 further includes wetting a first surface of the separator with a non-aqueous liquid electrolyte at step 14; and coating the first surface of the separator with a carbon coating at step 15. The method 10 optionally includes placing a second electrode on the semi-solid electrode at step 16, and inserting a separator therebetween, and charging and discharging the electrochemical cell in a horizontal orientation at step 17.
[0032] Step 11 includes combining the active material with the conductive material and the non-aqueous liquid electrolyte to form a semi-solid electrode. In some embodiments, the semi-solid electrode may include a cathode. In some embodiments, the semi-solid electrode may include an anode. In some embodiments, the semi-solid electrode material may be crushed and / or ground before mixing the semi-solid electrode material with the solvent. In some embodiments, the semi-solid electrode material may be crushed and / or ground when the semi-solid electrode material is mixed with the solvent. In some embodiments, the electrode slurry may be subjected to grinding and / or crushing. In some embodiments, the semi-solid electrode material may be subjected to screening before mixing the semi-solid electrode material with the solvent. In some embodiments, the semi-solid electrode material may be subjected to screening when the semi-solid electrode material is mixed with the solvent. Screening may separate larger particles from the semi-solid electrode. In some embodiments, the electrode slurry may be subjected to screening. In some embodiments, screening may include using a vibrating screen.
[0033] In some embodiments, the semi-solid electrode may include an anode material. In some embodiments, the anode material may include a tin metal alloy, such as Sn-Co-C, Sn-Fe-C, Sn-Mg-C or La-Ni-Sn alloy. In some embodiments, the anode material may include an amorphous oxide, such as SnO or SiO amorphous oxide. In some embodiments, the anode material may include a glass anode, such as Sn-Si-Al-BO, Sn-Sb-SO, SnO2-P2O5 or SnO-B2O3-P2O5-Al2O3 anode. In some embodiments, the anode material may include a metal oxide, such as CoO, SnO2 or V2O5. In some embodiments, the anode material may include a metal nitride, such as Li3N or Li2.6CoO.4N. In some embodiments, the anode material may include an anode active material selected from lithium metal, carbon, lithium carbon, lithium nitride, lithium alloy and silicon, bismuth, boron, gallium, indium, zinc, tin, antimony, aluminum, titanium oxide, molybdenum, germanium, manganese, niobium, vanadium, tantalum, gold, platinum, iron, copper, chromium, nickel, cobalt, zirconium, yttrium, molybdenum oxide, germanium oxide, silicon oxide, silicon carbide lithium alloy forming compound, any other high capacity material or its alloy and any other combination thereof. In some embodiments, the anode active material may include silicon and / or its alloy. In some embodiments, the anode active material may include tin and / or its alloy.
[0034] In some embodiments, the semi-solid electrode may include a cathode material. In some embodiments, the cathode material may include a general family of ordered rock salt compounds LiMO2, which includes compounds having α-NaFeO2 (so-called "layered compounds") or orthorhombic-LiMnO2 structure types or derivatives thereof with different crystal symmetries, atomic ordering, or partial metal or oxygen substitutions. M comprises at least one first-row transition metal, but may also include non-transition metals, including but not limited to Al, Ca, Mg, or Zr. Examples of such compounds include LiFePO4 (LFP), LiCoO2, Mg-doped LiCoO2, LiNiO2, Li(Ni, Co, Al)O2 (referred to as "NCA"), and Li(Ni, Mn, Co)O2 (referred to as "NMC"). In some embodiments, the cathode material may include a spinel structure such as LiMn2O4 and its derivatives, so-called "layered spinel nanocomposites" wherein the structure includes nano-regions having ordered rock salt and spinel ordering, olivine LiMPO4 and its derivatives (wherein M comprises one or more of Mn, Fe, Co or Ni), partially fluorinated compounds such as LiVPO4F, other "polyanionic" compounds as described below, and V2O5 and V6O 11 Vanadium oxide V x O yIn some embodiments, the cathode material may include a transition metal polyanion compound. In some embodiments, the cathode material may include an alkali metal transition metal oxide or a phosphate, and for example, the compound has a composition A x (M' 1-a M″ a ) y (XD4) z , A x (M' 1-a M" a ) y (DXD4) z or A x (M' 1-a M″ a ) y (X2D7) z , and having a value such as x, plus y(1-a) times one or more valences of M', plus y(a) times one or more valences of M", equals z times the valence of the XD4, X2D7 or DXD4 group; or comprising a combination (A 1-a M″ a ) x M' y (XD4) z ,(A 1-a M″ a ) x (M' y (DXD4)z(A 1-a M″ a ) a M' y (X2D7) z A compound of the type described herein, and its value is such that (1-a)x plus the number ax multiplied by one or more valence forms of M″ plus y multiplied by one or more valence forms of M′ is equal to z multiplied by the valence forms of the XD4, X2D7 or DXD4 group. In the compound, A is at least one of an alkali metal and hydrogen, M′ is a first-row transition metal, X is at least one of phosphorus, sulfur, arsenic, molybdenum and tungsten, M″ is any one of HA, IIIA, IVA, VA, VIA, VIIA, VIIIA, IB, IIB, IIIB, IVB, VB and VIB group metals, and D is at least one of oxygen, nitrogen, carbon or halogen. The positive electroactive material can be an olivine structure compound LiMPO4, wherein M is one or more of V, Cr, Mn, Fe, Co and Ni, wherein the compound is optionally doped at the Li, M or O position. The deficiency at the Li site is made up by adding a metal or metalloid, and the deficiency at the O site is made up by adding a halogen. In some embodiments, the positive electrode active material comprises a thermally stable, transition metal-doped transition metal lithium phosphate having an olivine structure and having the formula (Li 1-x Zx )MPO4, wherein M is one or more of V, Cr, Mn, Fe, Co and Ni, and Z is a non-alkali metal dopant such as one or more of Ti, Zr, Nb, Al or Mg, and x ranges from 0.005 to 0.05.
[0035] In some embodiments, the conductive material may include an allotrope of carbon, including activated carbon, hard carbon, soft carbon, Ketjen, carbon black, graphite carbon, carbon fiber, carbon microfiber, vapor grown carbon fiber (VGCF), fullerene carbon including "buckyballs", carbon nanotubes (CNTs), multi-walled carbon nanotubes (MWNTs), single-walled carbon nanotubes (SWNTs), graphene flakes or aggregates of graphene flakes, and materials containing fullerene fragments, or any combination thereof. In some embodiments, the active material, conductive material, and / or electrolyte solution may include any of the materials described in U.S. Pat. No. 9,437,864, filed on March 10, 2014, entitled "Asymmetric Battery Having a Semi-solid Cathode and High Energy Density Anode" ("the '864 patent"), the disclosure of which is hereby incorporated by reference in its entirety.
[0036] In some embodiments, the non-aqueous liquid electrolyte may include an electrolyte solvent and an electrolyte salt. In some embodiments, the electrolyte solvent may include vinylene carbonate (VC), 1,3 propane sultone (PS), ethyl propionate (EP), 1,3-propylene glycol cyclic sulfate (PSA / TS), fluoroethylene carbonate (FEC), ethylene sulfite (ES), tris(2-ethylhexyl) phosphate (TOP), 1,3,2-dioxathiolane 2,2-dioxide (DTD), ethyl acetate (EA), maleic anhydride (MA), ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), or a combination thereof. In some embodiments, the electrolyte salt may include lithium bis(oxalato) borate (LiBOB), lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl) imide (LiFSI), or any combination thereof.
[0037] In some embodiments, the concentration of the electrolyte salt in the electrolyte solution may be at least about 1.5 M, at least about 2 M, at least about 2.5 M, at least about 3 M, at least about 3.5 M, at least about 4 M, at least about 4.5 M, at least about 5 M, at least about 5.5 M, at least about 6 M, at least about 6.5 M, at least about 7 M, at least about 7.5 M, at least about 8 M, at least about 8.5 M, at least about 9 M, or at least about 9.5 M. In some embodiments, the concentration of the electrolyte salt in the electrolyte solution may be no greater than about 10 M, no greater than about 9.5 M, no greater than about 9 M, no greater than about 8.5 M, no greater than about 8 M, no greater than about 7.5 M, no greater than about 7 M, no greater than about 6.5 M, no greater than about 5 M, no greater than about 5.5 M, no greater than about 5 M, no greater than about 4.5 M, no greater than about 4 M, no greater than about 3.5 M, no greater than about 3 M, no greater than about 2.5 M, or no greater than about 2 M. Combinations of the above salt concentrations are also possible (e.g., at least about 1.5 M and not more than about 10 M or at least about 3 M and not more than about 5 M), including all values and ranges therebetween. In some embodiments, the concentration of the electrolyte salt in the electrolyte solution can be about 1.5 M, about 2 M, about 2.5 M, about 3 M, about 3.5 M, about 4 M, about 4.5 M, about 5 M, about 5.5 M, about 6 M, about 6.5 M, about 7 M, about 7.5 M, about 8 M, about 8.5 M, about 9 M, about 9.5 M, or about 10 M.
[0038] In some embodiments, the electrolyte may include a single salt. In some embodiments, the electrolyte may include about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10 salts, including all values and ranges therebetween. In some embodiments, the electrolyte salt may include LiFSi, LiPF6, or any combination thereof. For example, the electrolyte salt may include about 2M LiFSI. As another example, the electrolyte salt may include about 1.5M LiPF6 and about 0.5M LiFSI.
[0039] In some embodiments, the electrolyte may include a single electrolyte solvent. In some embodiments, the electrolyte may include about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9 or about 10 electrolyte solvents, including all values and ranges therebetween. In some embodiments, the electrolyte solvent may include EC, PC, EMC, MA or any combination thereof and in any ratio. For example, the electrolyte solvent may include EC / PC / EMC with a ratio of about 2 parts (by weight) EC and about 1 part PC and about 7 parts EMC. As another example, the electrolyte solvent may include EC / PC / EMC / MA with a ratio of about 2 parts EC and about 1 part PC and about 3 parts EMC and about 4 parts MA.
[0040] In some embodiments, the electrolyte may include an additive or a combination of additives. In some embodiments, the electrolyte may include about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5 wt%, about 0.6 wt%, about 0.7 wt%, about 0.8 wt%, about 0.9 wt%, about 1 wt%, about 1.5 wt%, about 2 wt%, about 2.5 wt%, about 3 wt%, about 3.5 wt%, about 4 wt%, about 4.5 wt%, about 5 wt%, about 5.5 wt%, about 6 wt%, about 6.5 wt%, about 7 wt%, about 7.5 wt%, about 8 wt%, about 8.5 wt%, about 9 wt%, about 9.5 wt%, or about 10 wt%, including all values and ranges therebetween. In some embodiments, the additive may include VC, DTD, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), lithium difluoro(oxalato)borate (LiDFOB), FEC, tris(trimethylsilyl)phosphate (TMSP8), tris(2,2,2-trifluoroethyl)borate (TTFEB), 1,4-butane sultone (BuS), lithium difluorophosphate (LiPO2F2), or any combination thereof. For example, the electrolyte may include about 0.5 wt% to about 2 wt% VC, about 1 wt% to about 1.5 wt% DTD, about 0.5 wt% to about 3 wt% TTE, and about 0.5 wt% to about 1 wt% LiDFOB. As another example, the electrolyte may include about 0.5wt% to about 2wt% VC, about 1wt% to about 1.5wt% DTD, about 0.5wt% to about 3wt% TTE, about 0.5wt% to about 1wt% LiDFOB, and about 0.1wt% to about 1wt% FEC. As another example, the electrolyte may include about 0.5wt% to about 2wt% VC, about 1wt% to about 1.5wt% DTD, about 0.5wt% to about 3wt% TTE, about 0.5wt% to about 1wt% LiDFOB, and about 0.1wt% to about 1wt% TMSP8. As another example, the electrolyte may include about 0.5wt% to about 2wt% VC, about 1wt% to about 1.5wt% DTD, and about 0.5wt% to about 2wt% TTFEB. As another example, the electrolyte may include about 0.5wt% to about 2wt% VC and about 0.5wt% to about 1wt% BuS. As another example, the electrolyte may include about 0.5 wt % to about 2 wt % VC and about 0.5 wt % to about 1 wt % LiPO2F2. As another example, the electrolyte may include about 0.5 wt % to about 2 wt % VC, about 0.5 wt % to about 1 wt % BuS, and about 0.5 wt % to about 1 wt % LiPO2F2.
[0041] In some embodiments, the active material, conductive material, and / or electrolyte solution may be combined by mixing, high shear mixing, planetary mixing, centrifugal planetary mixing, sigma mixing, crack attenuation mixing (CAM) mixing, drum mixing, or any combination thereof. In some embodiments, the active material, conductive material, and / or electrolyte solution may be mixed together with a mixing index of at least about 0.8, at least about 0.85, at least about 0.9, at least about 0.95, or at least about 0.975, including all values and ranges therebetween. In some embodiments, the active material, conductive material, and / or electrolyte solution may be combined by any of the mixing methods described in U.S. Patent Publication No. 2017 / 0162863 ('863 Publication), filed on September 15, 2016, entitled "Electrochemical Slurry Compositions and Methods for Preparing the Same," the entire disclosure of which is hereby incorporated by reference.
[0042] Step 12 includes placing a semi-solid electrode on the first current collector. In some embodiments, the semi-solid electrode can be distributed and / or extruded by a sheet extrusion die, a profiled sheet extrusion die, any nozzle, a single screw extruder, a twin screw extruder or an injection mold. In some embodiments, the viscosity of the semi-solid electrode (at 25° C.) can be at least about 100 Pa·s, at least about 150 Pa·s, at least about 200 Pa·s, at least about 250 Pa·s, at least about 300 Pa·s, at least about 350 Pa·s, at least about 400 Pa·s, at least about 450 Pa·s, at least about 500 Pa·s, at least about 550 Pa·s, at least about 600 Pa·s, at least about 650 Pa·s, at least about 700 Pa·s, at least about 750 Pa·s, at least about 800 Pa·s, at least about 850 Pa·s, at least about 900 Pa·s or at least about 950 Pa·s. In some embodiments, the viscosity of the semi-solid electrode may be no greater than about 1,000 Pa·s, no greater than about 950 Pa·s, no greater than about 900 Pa·s, no greater than about 850 Pa·s, no greater than about 800 Pa·s, no greater than about 750 Pa·s, no greater than about 700 Pa·s, no greater than about 650 Pa·s, no greater than about 600 Pa·s, no greater than about 550 Pa·s, no greater than about 500 Pa·s, no greater than about 450 Pa·s, no greater than about 400 Pa·s, no greater than about 350 Pa·s, no greater than about 300 Pa·s, no greater than about 250 Pa·s, no greater than about 200 Pa·s, or no greater than about 950 Pa·s. Combinations of the above viscosities are also possible (e.g., at least about 100 Pa·s and not more than about 1,000 Pa·s or at least about 300 Pa·s and not more than about 600 Pa·s), including all values and ranges therebetween. In some embodiments, the viscosity of the semi-solid electrode may be about 100 Pa·s, about 150 Pa·s, about 200 Pa·s, about 250 Pa·s, about 300 Pa·s, about 350 Pa·s, about 400 Pa·s, about 450 Pa·s, about 500 Pa·s, about 550 Pa·s, about 600 Pa·s, about 650 Pa·s, about 700 Pa·s, about 750 Pa·s, about 800 Pa·s, about 850 Pa·s, about 900 Pa·s, about 950 Pa·s, or about 1,000 Pa·s.
[0043] When the semi-solid electrode is disposed on the first current collector, the semi-solid electrode has a thickness. In some embodiments, the thickness of the semi-solid electrode can be at least about 100 μm, at least about 150 μm, at least about 200 μm, at least about 250 μm, at least about 300 μm, at least about 350 μm, at least about 400 μm, at least about 450 μm, at least about 500 μm, at least about 550 μm, at least about 600 μm, at least about 650 μm, at least about 700 μm, at least about 750 μm, at least about 800 μm, at least about 850 μm, at least about 900 μm, at least about 950 μm, at least about 1,000 μm, at least about 1,050 μm, or at least about 1,000 μm. In some embodiments, the present invention relates to a thickness of at least about 1 μm, at least about 1,100 μm, at least about 1,150 μm, at least about 1,200 μm, at least about 1,250 μm, at least about 1,300 μm, at least about 1,350 μm, at least about 1,400 μm, at least about 1,450 μm, at least about 1,500 μm, at least about 1,550 μm, at least about 1,600 μm, at least about 1,650 μm, at least about 1,700 μm, at least about 1,750 μm, at least about 1,800 μm, at least about 1,850 μm, at least about 1,900 μm or at least about 1,950 μm. In some embodiments, the thickness of the semi-solid electrode may be no greater than about 2,000 μm, no greater than about 1,950 μm, no greater than about 1,900 μm, no greater than about 1,850 μm, no greater than about 1,800 μm, no greater than about 1,750 μm, no greater than about 1,700 μm, no greater than about 1,650 μm, no greater than about 1,600 μm, no greater than about 1,550 μm, no greater than about 1,500 μm, no greater than about 1,450 μm, no greater than about 1,400 μm, no greater than about 1,350 μm, no greater than about 1,300 μm, no greater than about 1,250 μm, no greater than about 1,200 μm. μm, no more than about 1,150 μm, no more than about 1,100 μm, no more than about 1,050 μm, no more than about 1,000 μm, no more than about 950 μm, no more than about 900 μm, no more than about 850 μm, no more than about 800 μm, no more than about 750 μm, no more than about 700 μm, no more than about 650 μm, no more than about 600 μm, no more than about 550 μm, no more than about 500 μm, no more than about 450 μm, no more than about 400 μm, no more than about 350 μm, no more than about 300 μm, no more than about 250 μm, no more than about 200 μm or no more than about 150 μm. Combinations of the above thicknesses are also possible (eg, at least about 100 μm and not greater than about 2,000 μm or at least about 300 μm and not greater than about 1,000 μm), including all values and ranges therebetween.In some embodiments, the thickness of the semi-solid electrode can be about 100 μm, about 150 μm, about 200 μm, about 250 μm, about 300 μm, about 350 μm, about 400 μm, about 450 μm, about 500 μm, about 550 μm, about 600 μm, about 650 μm, about 700 μm, about 750 μm, about 800 μm, about 850 μm, about 900 μm, about 950 μm, about 1,000 μm, about 1,050 μm, about 1,100 μm, or about 1,000 μm. In some embodiments, the present invention relates to a nanostructured carbon foam having a thickness of about 100 μm, about 1,000 μm, about 1,150 μm, about 1,200 μm, about 1,250 μm, about 1,300 μm, about 1,350 μm, about 1,400 μm, about 1,450 μm, about 1,500 μm, about 1,550 μm, about 1,600 μm, about 1,650 μm, about 1,700 μm, about 1,750 μm, about 1,800 μm, about 1,850 μm, about 1,900 μm, about 1,950 μm or about 2,000 μm.
[0044] At step 13, method 10 optionally includes placing a second electrode onto the second current collector. In some embodiments, the second electrode may include an anode. In some embodiments, the second electrode may include a cathode. In some embodiments, the second electrode may include a semi-solid electrode. In some embodiments, the second electrode may include a solid or "conventional" electrode.
[0045] When the second electrode is placed on the second current collector, the second electrode has a thickness. In some embodiments, the thickness of the second electrode may be at least about 20 μm, at least about 30 μm, at least about 40 μm, at least about 50 μm, at least about 60 μm, at least about 70 μm, at least about 80 μm, or at least about 90 μm. In some embodiments, the thickness of the second electrode may be no more than about 100 μm, no more than about 90 μm, no more than about 80 μm, no more than about 70 μm, no more than about 60 μm, no more than about 50 μm, no more than about 40 μm, or no more than about 30 μm. Combinations of the above thicknesses of the second electrode are also possible (e.g., at least about 20 μm and no more than about 100 μm or at least about 40 μm and no more than about 80 μm), including all values and ranges therebetween. In some embodiments, the thickness of the second electrode may be about 20 μm, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 70 μm, about 80 μm, about 90 μm, or about 100 μm.
[0046] In step 14, method 10 includes wetting the first surface of the separator with a non-aqueous liquid electrolyte. In some embodiments, wetting can be performed by spraying, brushing, injection (e.g., with a syringe), inkjet printing, slot die dripping, coating, or any other suitable application method. In some embodiments, the non-aqueous liquid electrolyte applied to the first surface of the separator can have a concentration that is the same as or substantially similar to the non-aqueous liquid electrolyte included in the semi-solid electrode. In some embodiments, both sides of the separator can be coated with a non-aqueous liquid electrolyte.
[0047] Step 15 includes coating the first surface of the diaphragm with a carbon coating. In some embodiments, the carbon coating may include hard carbon, disordered carbon, graphite, graphite carbon or non-graphite carbon, amorphous carbon, mesophase carbon (mesocarbon), microbeads, soft carbon, activated carbon, graphite-hard carbon mixture or any combination thereof. In some embodiments, the carbon coating may include a crystalline portion and an amorphous portion. In some embodiments, the carbon coating may include activated carbon, Ketjen black, carbon nanotubes, carbon fibers or any combination thereof. In some embodiments, a nonaqueous electrolyte may promote the attachment of the carbon coating to the first surface of the carbon coating.
[0048] Step 16 is optional and includes placing a second electrode onto the semi-solid electrode and inserting a separator between the second electrode and the semi-solid electrode. This forms an electrochemical cell. The first surface of the separator (i.e., the surface of the separator coated with the non-aqueous liquid electrolyte solution and the carbon coating) is in contact with the semi-solid electrode. The non-aqueous liquid electrolyte solution and the carbon coating promote electrochemical contact between the semi-solid electrode and the separator.
[0049] Step 17 is optional and includes charging and discharging the electrochemical cell in a horizontal orientation. In other words, the electrochemical cell is charged and discharged while the electrode is oriented horizontally so that gravity acts in the thickness direction of the electrode. Gravity forms a density gradient and a salt concentration gradient in the high viscosity semi-solid electrode. In some embodiments, the density gradient can be generated by a magnetic field. In some embodiments, the density gradient can be generated by heating the semi-solid electrode. In some embodiments, the density gradient can be generated by centrifugal force. In some embodiments, the electrochemical cell can be rotated about a central axis while the electrochemical cell is in operation. In some embodiments, a plurality of electrochemical cells can be rotated about a central axis to form a density gradient.
[0050] In some embodiments, the electrochemical cell can be charged at a rate of at least about 1C, at least about 1.5C, at least about 2C, at least about 2.5C, at least about 3C, at least about 3.5C, at least about 4C, at least about 4.5C, at least about 5C, at least about 5.5C, at least about 6C, at least about 6.5C, at least about 7C, at least about 7.5C, at least about 8C, at least about 8.5C, at least about 9C, at least about 9.5C, or at least about 10C, including all values and ranges therebetween. In some embodiments, the electrochemical cell can be discharged at a rate of at least about 1C, at least about 1.5C, at least about 2C, at least about 2.5C, at least about 3C, at least about 3.5C, at least about 4C, at least about 4.5C, at least about 5C, at least about 5.5C, at least about 6C, at least about 6.5C, at least about 7C, at least about 7.5C, at least about 8C, at least about 8.5C, at least about 9C, at least about 9.5C, or at least about 10C, including all values and ranges therebetween.
[0051] Figure 2 is a block diagram of an electrochemical cell 200 according to an embodiment. As shown, the electrochemical cell 200 includes an anode 210 disposed on an anode current collector 220, a cathode 230 disposed on a cathode current collector 240, and a separator 250 disposed between the anode 210 and the cathode 230. A carbon coating 260 is optionally disposed between the cathode 230 and the separator 250.
[0052] Anode 210 includes an anode active material. In some embodiments, anode 210 may include any of the anode materials listed above. In some embodiments, anode 210 may include a semi-solid anode. In some embodiments, the electrolyte salt concentration of anode 210 may be at least about 500 mol / m 3 , at least about 1,000 mol / m 3 , at least about 1,500 mol / m 3 , at least about 2,000 mol / m 3 , at least about 2,100 mol / m 3 , at least about 2,200 mol / m 3 , at least about 2,300 mol / m 3 , at least about 2,400 mol / m 3 , at least about 2,500 mol / m 3 , at least about 3,000 mol / m 3 , at least about 3,500 mol / m 3 , at least about 4,000 mol / m 3 , at least about 4,500 mol / m 3 , at least about 5,000 mol / m 3, at least about 5,500 mol / m 3 , at least about 6,000 mol / m 3 , at least about 6,500 mol / m 3 , at least about 7,000 mol / m 3 , at least about 7,500 mol / m 3 , at least about 8,000 mol / m 3 , at least about 8,500 mol / m 3 , at least about 9,000 mol / m 3 or at least about 9,500 mol / m 3 In some embodiments, the electrolyte salt concentration of anode 210 may be no greater than about 10,000 mol / m 3 , not more than about 9,500 mol / m 3 , not more than about 9,000 mol / m 3 , not more than about 8,500 mol / m 3 , not more than about 8,000 mol / m 3 , not more than about 7,500 mol / m 3 , not more than about 7,000 mol / m 3 , not more than about 6,500 mol / m 3 , not more than about 6,000 mol / m 3 , not more than about 5,500 mol / m 3 , not more than about 5,000 mol / m 3 , not more than about 4,500 mol / m 3 , not more than about 4,000 mol / m 3 , not more than about 3,500 mol / m 3 , not more than about 3,000 mol / m 3 , not more than about 2,500 mol / m 3 , not more than about 2,400 mol / m 3 , not more than about 2,300 mol / m 3 , not more than about 2,200 mol / m 3 , not more than about 2,100 mol / m 3 , not more than about 2,000 mol / m 3 , not more than about 1,500 mol / m 3 or not more than about 1,000 mol / m 3 Combinations of the above electrolyte salt concentrations in anode 210 are also possible (e.g., at least about 500 mol / m 3 and not more than about 10,000 mol / m 3or at least about 2,000 mol / m 3 and not more than about 5,000 mol / m 3 ), including all values and ranges therebetween. In some embodiments, the electrolyte salt concentration of the anode 210 may be about 500 mol / m 3 , about 1,000 mol / m 3 , about 1,500 mol / m 3 , about 2,000 mol / m 3 , about 2,100 mol / m 3 , about 2,200 mol / m 3 , about 2,300 mol / m 3 , about 2,400 mol / m 3 , about 2,500 mol / m 3 , about 3,000 mol / m 3 , about 3,500 mol / m 3 , about 4,000 mol / m 3 , about 4,500 mol / m 3 , about 5,000 mol / m 3 , about 5,500 mol / m 3 , about 6,000 mol / m 3 , about 6,500 mol / m 3 , about 7,000 mol / m 3 , about 7,500 mol / m 3 , about 8,000 mol / m 3 , about 8,500 mol / m 3 , about 9,000 mol / m 3 , about 9,500 mol / m 3 or about 10,000 mol / m 3 In some embodiments, the electrolyte salt concentration may be measured directly. In some embodiments, the electrolyte salt concentration may be estimated by simulation based on finite element modeling.
[0053] In some embodiments, anode 210 may have an electrolyte salt concentration gradient along the thickness of anode 210. In some embodiments, the concentration gradient may exist when electrochemical cell 200 is charged. In some embodiments, the concentration gradient may exist when electrochemical cell 200 is discharged. In some embodiments, the concentration gradient may exist when electrochemical cell 200 is dormant. In some embodiments, the average electrolyte salt concentration gradient of anode 210 may be at least about 1×10 7 mol / m 4 , at least about 1.1x10 7 mol / m4 , at least about 1.2x10 7 mol / m 4 , at least about 1.3x10 7 mol / m 4 , at least about 1.4x10 7 mol / m 4 , at least about 1.5x10 7 mol / m 4 , at least about 1.6x10 7 mol / m 4 , at least about 1.7x10 7 mol / m 4 , at least about 1.8x10 7 mol / m 4 , at least about 1.9x10 7 mol / m 4 , at least about 2x10 7 mol / m 4 , at least about 2.1x10 7 mol / m 4 , at least about 2.2x10 7 mol / m 4 , at least about 2.3x10 7 mol / m 4 , at least about 2.4x10 7 mol / m 4 , at least about 2.5x10 7 mol / m 4 , at least about 2.6x10 7 mol / m 4 , at least about 2.7x10 7 mol / m 4 , at least about 2.8x10 7 mol / m 4 , at least about 2.9x10 7 mol / m 4 , at least about 3x10 7 mol / m 4 , at least about 3.1x10 7 mol / m 4 , at least about 3.2x10 7 mol / m 4 , at least about 3.3x10 7 mol / m 4 , at least about 3.4x10 7 mol / m 4 , at least about 3.5x10 7 mol / m 4 , at least about 3.6x107 mol / m 4 , at least about 3.7x10 7 mol / m 4 , at least about 3.8x10 7 mol / m 4 , at least about 3.9x10 7 mol / m 4 , at least about 4x10 7 mol / m 4 , at least about 4.1x10 7 mol / m 4 , at least about 4.2x10 7 mol / m 4 , at least about 4.3x10 7 mol / m 4 , at least about 4.4x10 7 mol / m 4 , at least about 4.5x10 7 mol / m 4 , at least about 4.6x10 7 mol / m 4 , at least about 4.7x10 7 mol / m 4 , at least about 4.8x10 7 mol / m 4 , at least about 4.9x10 7 mol / m 4 In some embodiments, the average electrolyte salt concentration gradient of the anode 210 may be no greater than about 5×10 7 mol / m 4 , not larger than approximately 4.9x10 7 mol / m 4 , not larger than approximately 4.8x10 7 mol / m 4 , not larger than about 4.7x10 7 mol / m 4 , not larger than approximately 4.6x10 7 mol / m 4 , not larger than about 4.5x10 7 mol / m 4 , not larger than approximately 4.4x10 7 mol / m 4 , not larger than about 4.3x10 7 mol / m 4 , not more than about 4.2x10 7 mol / m 4 , not more than about 4.1x10 7 mol / m4 , not larger than about 4x10 7 mol / m 4 , not larger than about 3.9x10 7 mol / m 4 , not larger than about 3.8x10 7 mol / m 4 , not larger than about 3.7x10 7 mol / m 4 , not larger than about 3.6x10 7 mol / m 4 , not larger than about 3.5x10 7 mol / m 4 , not larger than about 3.4x10 7 mol / m 4 , not more than about 3.3x10 7 mol / m 4 , not more than about 3.2x10 7 mol / m 4 , not more than about 3.1x10 7 mol / m 4 , not more than about 3x10 7 mol / m 4 , not larger than about 2.9x10 7 mol / m 4 , not larger than about 2.8x10 7 mol / m 4 , not larger than about 2.7x10 7 mol / m 4 , not more than about 2.6x10 7 mol / m 4 , not larger than about 2.5x10 7 mol / m 4 , not larger than about 2.4x10 7 mol / m 4 , not more than about 2.3x10 7 mol / m 4 , not more than about 2.2x10 7 mol / m 4 , not more than about 2.1x10 7 mol / m 4 , not more than about 2x10 7 mol / m 4 , not more than about 1.9 x 10 7 mol / m 4 , not larger than about 1.8x10 7 mol / m 4 , not more than about 1.7x107 mol / m 4 , not more than about 1.6x10 7 mol / m 4 , not more than about 1.5x10 7 mol / m 4 , not more than about 1.4x10 7 mol / m 4 , not more than about 1.3x10 7 mol / m 4 , not more than about 1.2x10 7 mol / m 4 or not greater than about 1.1x10 7 mol / m 4 .
[0054] Combinations of the above average electrolyte salt concentration gradients are also possible (e.g., at least about 1×10 7 mol / m 4 and no larger than about 5x10 7 mol / m 4 or at least about 2 mol / m 4 and not more than about 4 mol / m 4 ), including all values and ranges therebetween. In some embodiments, the average electrolyte salt concentration gradient of the anode 210 may be about 1.0×10 7 mol / m 4 , about 1.1x10 7 mol / m 4 , about 1.2x10 7 mol / m 4 , about 1.3x10 7 mol / m 4 , about 1.4x10 7 mol / m 4 , about 1.5x10 7 mol / m 4 , about 1.6x10 7 mol / m 4 , about 1.7x10 7 mol / m 4 , about 1.8x10 7 mol / m 4 , about 1.9x10 7 mol / m 4 , about 2.0x10 7 mol / m 4 , about 2.1x10 7 mol / m 4 , about 2.2x10 7 mol / m4 , about 2.3x10 7 mol / m 4 , about 2.4x10 7 mol / m 4 , about 2.5x10 7 mol / m 4 , about 2.6x10 7 mol / m 4 , about 2.7x10 7 mol / m 4 , about 2.8x10 7 mol / m 4 , about 2.9x10 7 mol / m 4 , about 3.0x10 7 mol / m 4 , about 3.1x10 7 mol / m 4 , about 3.2x10 7 mol / m 4 , about 3-3x10 7 mol / m 4 , about 3.4x10 7 mol / m 4 , about 3.5x10 7 mol / m 4 , about 3.6x10 7 mol / m 4 , about 3.7x10 7 mol / m 4 , about 3.8x10 7 mol / m 4 , about 3.9x10 7 mol / m 4 , about 4.0x10 7 mol / m 4 , about 4.1x10 7 mol / m 4 , about 4.2x10 7 mol / m 4 , about 4.3x10 7 mol / m 4 , about 4.4x10 7 mol / m 4 , about 4.5x10 7 mol / m 4 , about 4.6x10 7 mol / m 4 , about 4.7x10 7 mol / m 4 , about 4.8x107 mol / m 4 , about 4.9x10 7 mol / m 4 or about 5.0x10 7 mol / m 4 .
[0055] In some embodiments, anode 210 may have a density gradient. In some embodiments, a density gradient may exist when electrochemical cell 200 is charged. In some embodiments, a density gradient may exist when electrochemical cell 200 is discharged. In some embodiments, a density gradient may exist when electrochemical cell 200 is dormant. In some embodiments, the average density gradient of anode 210 may be at least about 1×10 5 kg / m 4 , at least about 2x10 5 kg / m 4 , at least about 3x10 5 kg / m 4 , at least about 4x10 5 kg / m 4 , at least about 5x10 5 kg / m 4 , at least about 6x10 5 kg / m 4 , at least about 7x10 5 kg / m 4 , at least about 8x10 5 kg / m 4 , at least about 9x10 5 kg / m 4 , at least about 1x10 6 kg / m 4 , at least about 2x10 6 kg / m 4 , at least about 3x10 6 kg / m 4 , at least about 4x10 6 kg / m 4 , at least about 5x10 6 kg / m 4 , at least about 6x10 6 kg / m 4 , at least about 7x10 6 kg / m 4 , at least about 8x10 6 kg / m 4 , at least about 9x10 6 kg / m 4 , at least about 1x10 7 kg / m 4 , at least about 2x107 kg / m 4 , at least about 3x10 7 kg / m 4 , at least about 4x10 7 kg / m 4 , at least about 5x10 7 kg / m 4 , at least about 6x10 7 kg / m 4 , at least about 7x10 7 kg / m 4 , at least about 8x10 7 kg / m 4 , at least about 9x10 7 kg / m 4 , at least about 1x10 8 kg / m 4 , at least about 2x10 8 kg / m 4 , at least about 3x10 8 kg / m 4 , at least about 4x10 8 kg / m 4 , at least about 5x10 8 kg / m 4 , at least about 6x10 8 kg / m 4 , at least about 7x10 8 kg / m 4 , at least about 8x10 8 kg / m 4 Or at least about 9x10 8 kg / m 4 In some embodiments, the average concentration gradient of the anode 210 may be no greater than about 1×10 9 kg / m 4 , no larger than about 9x10 8 kg / m 4 , no larger than about 8x10 8 kg / m 4 , not larger than about 7x10 8 kg / m 4 , not larger than about 6x10 8 kg / m 4 , not larger than about 5x10 8 kg / m 4 , not larger than about 4x10 8 kg / m 4 , not more than about 3x10 8 kg / m 4 , not more than about 2x10 8 kg / m4 , not more than about 1x10 8 kg / m 4 , no larger than about 9x10 7 kg / m 4 , no larger than about 8x10 7 kg / m 4 , not larger than about 7x10 7 kg / m 4 , not larger than about 6x10 7 kg / m 4 , not larger than about 5x10 7 kg / m 4 , not larger than about 4x10 7 kg / m 4 , not more than about 3x10 7 kg / m 4 , not more than about 2x10 7 kg / m 4 , not more than about 1x10 7 kg / m 4 , no larger than about 9x10 6 kg / m 4 , no larger than about 8x10 6 kg / m 4 , not larger than about 7x10 6 kg / m 4 , not larger than about 6x10 6 kg / m 4 , not larger than about 5x10 6 kg / m 4 , not larger than about 4x10 6 kg / m 4 , not more than about 3x10 6 kg / m 4 , not more than about 2x10 6 kg / m 4 , not more than about 1x10 6 kg / m 4 , no larger than about 9x10 5 kg / m 4 , no larger than about 8x10 5 kg / m 4 , not larger than about 7x10 5 kg / m 4 , not larger than about 6x10 s kg / m 4 , not larger than about 5x10 5 kg / m 4 , not larger than about 4x10 s kg / m 4 , not more than about 3x105 kg / m 4 or no larger than about 2x10 5 kg / m 4 .
[0056] Combinations of the above average concentration gradients are also possible (e.g., at least about 1×10 5 kg / m 4 and no larger than about 1x10 9 kg / m 4 Or at least about 1x10 6 kg / m 4 and no larger than about 1x10 8 kg / m 4 ), including all values and ranges therebetween. In some embodiments, the average concentration gradient of the anode 210 may be about 1×10 5 kg / m 4 , about 2x10 5 kg / m 4 , about 3x10 5 kg / m 4 , about 4x10 5 kg / m 4 , about 5x10 5 kg / m 4 , about 6x10 5 kg / m 4 , about 7x10 5 kg / m 4 , about 8x10 5 kg / m 4 , about 9x10 5 kg / m 4 , about 1x10 6 kg / m 4 , about 2x10 6 kg / m 4 , about 3x10 6 kg / m 4 , about 4x10 6 kg / m 4 , about 5x10 6 kg / m 4 , about 6x10 6 kg / m 4 , about 7x10 6 kg / m 4 , about 8x10 6 kg / m 4 , about 9x10 6 kg / m 4 , about 1x10 7 kg / m 4 , about 2x107 kg / m 4 , about 3x10 7 kg / m 4 , about 4x10 7 kg / m 4 , about 5x10 7 kg / m 4 , about 6x10 7 kg / m 4 , about 7x10 7 kg / m 4 , about 8x10 7 kg / m 4 , about 9x10 7 kg / m 4 , about 1x10 8 kg / m 4 , about 2x10 8 kg / m 4 , about 3x10 8 kg / m 4 , about 4x10 8 kg / m 4 , about 5x10 8 kg / m 4 , about 6x10 8 kg / m 4 , about 7x10 8 kg / m 4 , about 8x10 8 kg / m 4 , about 9x10 8 kg / m 4 or about 1x10 9 kg / m 4 .
[0057] In some embodiments, the viscosity of the anode 210 (at 25° C.) can be at least about 100 Pa·s, at least about 150 Pa·s, at least about 200 Pa·s, at least about 250 Pa·s, at least about 300 Pa·s, at least about 350 Pa·s, at least about 400 Pa·s, at least about 450 Pa·s, at least about 500 Pa·s, at least about 550 Pa·s, at least about 600 Pa·s, at least about 650 Pa·s, at least about 700 Pa·s, at least about 750 Pa·s, at least about 800 Pa·s, at least about 850 Pa·s, at least about 900 Pa·s, or at least about 950 Pa·s. In some embodiments, the viscosity of the anode 210 may be no greater than about 1,000 Pa·s, no greater than about 950 Pa·s, no greater than about 900 Pa·s, no greater than about 850 Pa·s, no greater than about 800 Pa·s, no greater than about 750 Pa·s, no greater than about 700 Pa·s, no greater than about 650 Pa·s, no greater than about 600 Pa·s, no greater than about 550 Pa·s, no greater than about 500 Pa·s, no greater than about 450 Pa·s, no greater than about 400 Pa·s, no greater than about 350 Pa·s, no greater than about 300 Pa·s, no greater than about 250 Pa·s, no greater than about 200 Pa·s, or no greater than about 950 Pa·s. Combinations of the above viscosities are also possible (e.g., at least about 100 Pa·s and not more than about 1,000 Pa·s or at least about 300 Pa·s and not more than about 600 Pa·s), including all values and ranges therebetween. In some embodiments, the viscosity of anode 210 may be about 100 Pa·s, about 150 Pa·s, about 200 Pa·s, about 250 Pa·s, about 300 Pa·s, about 350 Pa·s, about 400 Pa·s, about 450 Pa·s, about 500 Pa·s, about 550 Pa·s, about 600 Pa·s, about 650 Pa·s, about 700 Pa·s, about 750 Pa·s, about 800 Pa·s, about 850 Pa·s, about 900 Pa·s, about 950 Pa·s, or about 1,000 Pa·s.
[0058] In some embodiments, anode 210 may have a viscosity gradient. In some embodiments, a viscosity gradient may exist when electrochemical cell 200 is charged. In some embodiments, a viscosity gradient may exist when electrochemical cell 200 is discharged. In some embodiments, a viscosity gradient may exist when electrochemical cell 200 is dormant. In some embodiments, the average viscosity gradient of anode 210 may be at least about 1×10 5 Pa·s / m, at least about 2x10 5 Pa·s / m, at least about 3x10 5 Pa·s / m, at least about 4x10 5Pa·s / m, at least about 5x10 5 Pa·s / m, at least about 6x10 5 Pa·s / m, at least about 7x10 5 Pa·s / m, at least about 8x10 5 Pa·s / m, at least about 9x10 5 Pa·s / m, at least about 1x10 6 Pa·s / m, at least about 2x10 6 Pa·s / m, at least about 3x10 6 Pa·s / m, at least about 4x10 6 Pa·s / m, at least about 5x10 6 Pa·s / m, at least about 6x10 6 Pa·s / m, at least about 7x10 6 Pa·s / rn, at least about 8x10 6 Pa·s / m, at least about 9x10 6 Pa·s / rn, at least about 1x10 7 Pa·s / m, at least about 2x10 7 Pa·s / m, at least about 3x10 7 Pa·s / m, at least about 4x10 7 Pa·s / m, at least about 5x10 7 Pa·s / m, at least about 6x10 7 Pa·s / m, at least about 7x10 7 Pa·s / m, at least about 8x10 7 Pa·s / m, at least about 9x10 7 Pa·s / m, at least about 1x10 8 Pa·s / rn, at least about 2x10 8 Pa·s / rn, at least about 3x10 8 Pa·s / m, at least about 4x10 8 Pa·s / m, at least about 5x10 8 Pa·s / m, at least about 6x10 8 Pa·s / m, at least about 7x10 8 Pa·s / m, at least about 8x10 8 Pa·s / m or at least about 9x10 8 In some embodiments, the average viscosity gradient of the anode 210 may be no greater than about 1×10 9 Pa·s / m, not more than about 9x10 8 Pa·s / m, not more than about 8x10 8 Pa·s / m, not more than about 7x10 8Pa·s / m, not more than about 6x10 8 Pa·s / m, not more than about 5x10 8 Pa·s / m, not more than about 4x10 8 Pa·s / m, not more than about 3x10 8 Pa·s / rn, not more than about 2x10 8 Pa·s / m, not more than about 1x10 8 Pa·s / m, not more than about 9x10 7 Pa·s / m, not more than about 8x10 7 Pa·s / m, not more than about 7x10 7 Pa·s / m, not more than about 6x10 7 Pa·s / m, not more than about 5x10 7 Pa·s / m, not more than about 4x10 7 Pa·s / m, not more than about 3x10 7 Pa·s / m, not more than about 2x10 7 Pa·s / m, not more than about 1x10 7 Pa·s / m, not more than about 9x10 6 Pa·s / m, not more than about 8x10 6 Pa·s / m, not more than about 7x10 6 Pa·s / m, not more than about 6x10 6 Pa·s / m, not more than about 5x10 6 Pa·s / m, not more than about 4x10 6 Pa·s / m, not more than about 3x10 6 Pa·s / m, not more than about 2x10 6 Pa·s / m, not more than about 1x10 6 Pa·s / m, not more than about 9x10 5 Pa·s / m, not more than about 8x10 5 Pa·s / m, not more than about 7x10 5 Pa·s / m, not more than about 6x10 5 Pa·s / m, not more than about 5x10 s Pa·s / m, not more than about 4x10 s Pa·s / m, not more than about 3x10 5 Pa·s / m or not more than about 2x10 5 Pa·s / m.
[0059] Combinations of the above average viscosity gradients are also possible (e.g., at least about 1×10 s Pa·s / m and not greater than about 1x10 9Pa·s / m or at least about 1x10 6 Pa·s / rn and not greater than about 1x10 8 Pa·s / m), including all values and ranges therebetween. In some embodiments, the average viscosity gradient of the anode 210 may be about 1×10 s Pa·s / m, about 2x10 s Pa·s / m, about 3x10 5 Pa·s / m, about 4x10 5 Pa·s / m, about 5x10 s Pa·s / m, about 6x10 s Pa·s / m, about 7x10 5 Pa·s / m, about 8x10 5 Pa·s / m, about 9x10 5 Pa·s / m, about 1x10 6 Pa·s / m, about 2x10 6 Pa·s / m, about 3x10 6 Pa·s / m, about 4x10 6 Pa·s / m, about 5x10 6 Pa·s / m, about 6x10 6 Pa·s / m, about 7x10 6 Pa·s / m, about 8x10 6 Pa·s / m, about 9x10 6 Pa·s / m, about 1x10 7 Pa·s / m, about 2x10 7 Pa·s / m, about 3x10 7 Pa·s / m, about 4x10 7 Pa·s / m, about 5x10 7 Pa·s / m, about 6x10 7 Pa·s / m, about 7x10 7 Pa·s / m, about 8x10 7 Pa·s / m, about 9x10 7 Pa·s / m, about 1x10 8 Pa·s / rn, about 2x10 8 Pa·s / m, about 3x10 8 Pa·s / m, about 4x10 8 Pa·s / m, about 5x10 8 Pa·s / m, about 6x10 8 Pa·s / m, about 7x10 8 Pa·s / m, about 8x10 8 Pa·s / m, about 9x10 8Pa·s / m or about 1x10 9 Pa·s / m.
[0060] In some embodiments, the anode current collector 220 may be made of copper, aluminum, titanium, or any combination thereof. In some embodiments, the thickness of the anode current collector 220 may be at least about 1 μm, at least about 2 μm, at least about 3 μm, at least about 4 μm, at least about 5 μm, at least about 10 μm, at least about 15 μm, at least about 20 μm, at least about 25 μm, at least about 30 μm, at least about 35 μm, at least about 40 μm, or at least about 45 μm. In some embodiments, the thickness of the anode current collector 220 may be no greater than about 50 μm, no greater than about 45 μm, no greater than about 40 μm, no greater than about 35 μm, no greater than about 30 μm, no greater than about 25 μm, no greater than about 20 μm, no greater than about 15 μm, no greater than about 10 μm, no greater than about 5 μm, no greater than about 4 μm, no greater than about 3 μm, or no greater than about 2 μm. Combinations of the above thicknesses of the anode current collector 220 are also possible (e.g., at least about 1 μm and not more than about 50 μm or at least about 5 μm and not more than about 20 μm), including all values and ranges therebetween. In some embodiments, the thickness of the anode current collector 220 may be about 1 μm, about 2 μm, about 3 μm, about 4 μm, about 5 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, about 40 μm, about 45 μm, or about 50 μm.
[0061] In some embodiments, cathode 230 may include a semi-solid cathode. In some embodiments, cathode 230 may have a thickness of at least about 100 μm, at least about 150 μm, at least about 200 μm, at least about 250 μm, at least about 300 μm, at least about 350 μm, at least about 400 μm, at least about 450 μm, at least about 500 μm, at least about 550 μm, at least about 600 μm, at least about 650 μm, at least about 700 μm, at least about 750 μm, at least about 800 μm, at least about 850 μm, at least about 900 μm, at least about 950 μm, at least about 1,000 μm, at least about 1,050 μm, or at least about 1,000 μm. In some embodiments, the present invention relates to a thickness of at least about 1 μm, at least about 1,100 μm, at least about 1,150 μm, at least about 1,200 μm, at least about 1,250 μm, at least about 1,300 μm, at least about 1,350 μm, at least about 1,400 μm, at least about 1,450 μm, at least about 1,500 μm, at least about 1,550 μm, at least about 1,600 μm, at least about 1,650 μm, at least about 1,700 μm, at least about 1,750 μm, at least about 1,800 μm, at least about 1,850 μm, at least about 1,900 μm or at least about 1,950 μm. In some embodiments, the thickness of cathode 230 may be no greater than about 2,000 μm, no greater than about 1,950 μm, no greater than about 1,900 μm, no greater than about 1,850 μm, no greater than about 1,800 μm, no greater than about 1,750 μm, no greater than about 1,700 μm, no greater than about 1,650 μm, no greater than about 1,600 μm, no greater than about 1,550 μm, no greater than about 1,500 μm, no greater than about 1,450 μm, no greater than about 1,400 μm, no greater than about 1,350 μm, no greater than about 1,300 μm, no greater than about 1,250 μm, no greater than about 1,200 μm, or no greater than about 1,300 μm. μm, no more than about 1,150 μm, no more than about 1,100 μm, no more than about 1,050 μm, no more than about 1,000 μm, no more than about 950 μm, no more than about 900 μm, no more than about 850 μm, no more than about 800 μm, no more than about 750 μm, no more than about 700 μm, no more than about 650 μm, no more than about 600 μm, no more than about 550 μm, no more than about 500 μm, no more than about 450 μm, no more than about 400 μm, no more than about 350 μm, no more than about 300 μm, no more than about 250 μm, no more than about 200 μm or no more than about 150 μm. Combinations of the above thicknesses are also possible (eg, at least about 100 μm and not greater than about 2,000 μm or at least about 300 μm and not greater than about 1,000 μm), including all values and ranges therebetween.In some embodiments, the thickness of cathode 230 can be about 100 μm, about 150 μm, about 200 μm, about 250 μm, about 300 μm, about 350 μm, about 400 μm, about 450 μm, about 500 μm, about 550 μm, about 600 μm, about 650 μm, about 700 μm, about 750 μm, about 800 μm, about 850 μm, about 900 μm, about 950 μm, about 1,000 μm, about 1,050 μm, about 1, 100μm, about 1,150μm, about 1,200μm, about 1,250μm, about 1,300μm, about 1,350μm, about 1,400μm, about 1,450μm, about 1,500μm, about 1,550μm, about 1,600μm, about 1,650μm, about 1,700μm, about 1,750μm, about 1,800μm, about 1,850μm, about 1,900μm, about 1,950μm or about 2,000μm.
[0062] In some embodiments, the electrolyte salt concentration of cathode 230 may be at least about 1,000 mol / m 3 , at least about 1,500 mol / m 3 , at least about 2,000 mol / m 3 , at least about 2,500 mol / m 3 , at least about 3,000 mol / m 3 , at least about 3,500 mol / m 3 , at least about 4,000 mol / m 3 , at least about 4,500 mol / m 3 , at least about 5,000 mol / m 3 , at least about 5,500 mol / m 3 , at least about 6,000 mol / m 3 , at least about 6,500 mol / m 3 , at least about 7,000 mol / m 3 , at least about 7,500 mol / m 3 , at least about 8,000 mol / m 3 , at least about 8,500 mol / m 3 , at least about 9,000 mol / m 3 or at least about 9,500 mol / m 3 In some embodiments, the electrolyte salt concentration of cathode 230 may be no greater than about 10,000 mol / m 3 , not more than about 9,500 mol / m 3 , not more than about 9,000 mol / m 3 , not more than about 8,500 mol / m3 , not more than about 8,000 mol / m 3 , not more than about 7,500 mol / m 3 , not more than about 7,000 mol / m 3 , not more than about 6,500 mol / m 3 , not more than about 6,000 mol / m 3 , not more than about 5,500 mol / m 3 , not more than about 5,000 mol / m 3 , not more than about 4,500 mol / m 3 , not more than about 4,000 mol / m 3 , not more than about 3,500 mol / m 3 , not more than about 3,000 mol / m 3 , or not more than about 2,500 mol / m 3 , not more than about 2,000 mol / m 3 or not more than about 1,500 mol / m 3 Combinations of the above electrolyte salt concentrations in cathode 230 are also possible (e.g., at least about 1,000 mol / m 3 and not more than about 10,000 mol / m 3 or at least about 2,000 mol / m 3 and not more than about 5,000 mol / m 3 ), including all values and ranges therebetween. In some embodiments, the electrolyte salt concentration of cathode 230 may be about 1,000 mol / m 3 , about 1,500 mol / m 3 , about 2,000 mol / m 3 , about 2,500 mol / m 3 , about 3,000 mol / m 3 , about 3,500 mol / m 3 , about 4,000 mol / m 3 , about 4,500 mol / m 3 , about 5,000 mol / m 3 , about 5,500 mol / m 3 , about 6,000 mol / m 3 , about 6,500 mol / m 3 , about 7,000 mol / m 3 , about 7,500 mol / m 3 , about 8,000 mol / m 3 , about 8,500 mol / m 3 , about 9,000 mol / m3 , about 9,500 mol / m 3 or about 10,000 mol / m 3 .
[0063] In some embodiments, cathode 230 can have an electrolyte salt concentration gradient along the thickness of cathode 230. In some embodiments, the concentration gradient can exist when electrochemical cell 200 is charging. In some embodiments, the concentration gradient can exist when electrochemical cell 200 is discharging. In some embodiments, the concentration gradient can exist when electrochemical cell 200 is dormant. In some embodiments, the average electrolyte salt concentration gradient of cathode 230 can be at least about 1.0x10 7 mol / m 4 , at least about 1.1x10 7 mol / m 4 , at least about 1.2x10 7 mol / m 4 , at least about 1.3x10 7 mol / m 4 , at least about 1.4x10 7 mol / m 4 , at least about 1.5x10 7 mol / m 4 , at least about 1.6x10 7 mol / m 4 , at least about 1.7x10 7 mol / m 4 , at least about 1.8x10 7 mol / m 4 , at least about 1.9x10 7 mol / m 4 , at least about 2.0x10 7 mol / m 4 , at least about 2.1x10 7 mol / m 4 , at least about 2.2x10 7 mol / m 4 , at least about 2.3x10 7 mol / m 4 , at least about 2.4x10 7 mol / m 4 , at least about 2.5x10 7 mol / m 4 , at least about 2.6x10 7 mol / m 4 , at least about 2.7x10 7 mol / m 4 , at least about 2.8x107 mol / m 4 , at least about 2.9x10 7 mol / m 4 , at least about 3.0x10 7 mol / m 4 , at least about 3.1x10 7 mol / m 4 , at least about 3.2x10 7 mol / m 4 , at least about 3.3x10 7 mol / m 4 , at least about 3.4x10 7 mol / m 4 , at least about 3.5x10 7 mol / m 4 , at least about 3.6x10 7 mol / m 4 , at least about 3.7x10 7 mol / m 4 , at least about 3.8x10 7 mol / m 4 , at least about 3.9x10 7 mol / m 4 , at least about 4.0x10 7 mol / m 4 , at least about 4.1x10 7 mol / m 4 , at least about 4.2x10 7 mol / m 4 , at least about 4.3x10 7 mol / m 4 , at least about 4.4x10 7 mol / m 4 , at least about 4.5x10 7 mol / m 4 , at least about 4.6x10 7 mol / m 4 , at least about 4.7x10 7 mol / m 4 , at least about 4.8x10 7 mol / m 4 , at least about 4.9x10 7 mol / m 4 In some embodiments, the average electrolyte salt concentration gradient of cathode 230 may be no greater than about 5.0 x 10 7 mol / m 4 , not larger than approximately 4.9x10 7 mol / m 4, not larger than approximately 4.8x10 7 mol / m 4 , not larger than about 4.7x10 7 mol / m 4 , not larger than approximately 4.6x10 7 mol / m 4 , not larger than about 4.5x10 7 mol / m 4 , not larger than approximately 4.4x10 7 mol / m 4 , not larger than about 4.3x10 7 mol / m 4 , not more than about 4.2x10 7 mol / m 4 , not more than about 4.1x10 7 mol / m 4 , not more than about 4.0x10 7 mol / m 4 , not larger than about 3.9x10 7 mol / m 4 , not larger than about 3.8x10 7 mol / m 4 , not larger than about 3.7x10 7 mol / m 4 , not larger than about 3.6x10 7 mol / m 4 , not larger than about 3.5x10 7 mol / m 4 , not larger than about 3.4x10 7 mol / m 4 , not more than about 3.3x10 7 mol / m 4 , not more than about 3.2x10 7 mol / m 4 , not more than about 3.1x10 7 mol / m 4 , not more than about 3.0x10 7 mol / m 4 , not larger than about 2.9x10 7 mol / m 4 , not larger than about 2.8x10 7 mol / m 4 , not larger than about 2.7x10 7 mol / m 4 , not more than about 2.6x10 7 mol / m 4 , not larger than about 2.5x10 7 mol / m4 , not larger than about 2.4x10 7 mol / m 4 , not more than about 2.3x10 7 mol / m 4 , not more than about 2.2x10 7 mol / m 4 , not more than about 2.1x10 7 mol / m 4 , not more than about 2.0x10 7 mol / m 4 , not larger than about 1.9x10 7 mol / m 4 , not larger than about 1.8x10 7 mol / m 4 , not more than about 1.7x10 7 mol / m 4 , not more than about 1.6x10 7 mol / m 4 , not more than about 1.5x10 7 mol / m 4 , not more than about 1.4x10 7 mol / m 4 , not more than about 1.3x10 7 mol / m 4 , not more than about 1.2x10 7 mol / m 4 or not greater than about 1.1x10 7 mol / m 4 .
[0064] Combinations of the above average electrolyte salt concentration gradients are also possible (e.g., at least about 1×10 7 mol / m 4 and not more than about 5 mol / m 4 or at least about 2 mol / m 4 and not more than about 4 mol / m 4 ), including all values and ranges therebetween. In some embodiments, the average electrolyte salt concentration gradient of cathode 230 may be about 1.0×10 7 mol / m 4 , about 1.1x10 7 mol / m 4 , about 1.2x10 7 mol / m 4 , about 1.3x10 7 mol / m 4 , about 1.4x10 7 mol / m 4, about 1.5x10 7 mol / m 4 , about 1.6x10 7 mol / m 4 , about 1.7x10 7 mol / m 4 , about 1.8x10 7 mol / m 4 , about 1.9x10 7 mol / m 4 , about 2.0x10 7 mol / m 4 , about 2.1x10 7 mol / m 4 , about 2.2x10 7 mol / m 4 , about 2.3x10 7 mol / m 4 , about 2.4x10 7 mol / m 4 , about 2.5x10 7 mol / m 4 , about 2.6x10 7 mol / m 4 , about 2.7x10 7 mol / m 4 , about 2.8x10 7 mol / m 4 , about 2.9x10 7 mol / m 4 , about 3.0x10 7 mol / m 4 , about 3.1x10 7 mol / m 4 , about 3.2x10 7 mol / m 4 , about 3.3x10 7 mol / m 4 , about 3.4x10 7 mol / m 4 , about 3.5x10 7 mol / m 4 , about 3.6x10 7 mol / m 4 , about 3.7x10 7 mol / m 4 , about 3.8x10 7 mol / m 4 , about 3.9x10 7 mol / m 4 , about 4.0x10 7 mol / m4 , about 4.1x10 7 mol / m 4 , about 4.2x10 7 mol / m 4 , about 4.3x10 7 mol / m 4 , about 4.4x10 7 mol / m 4 , about 4.5x10 7 mol / m 4 , about 4.6x10 7 mol / m 4 , about 4.7x10 7 mol / m 4 , about 4.8x10 7 mol / m 4 , about 4.9x10 7 mol / m 4 or about 5.0x10 7 mol / m 4 .
[0065] In some embodiments, cathode 230 may have a density gradient. In some embodiments, a density gradient may exist when electrochemical cell 200 is charging. In some embodiments, a density gradient may exist when electrochemical cell 200 is discharging. In some embodiments, a density gradient may exist when electrochemical cell 200 is dormant. In some embodiments, an average density gradient of cathode 230 may be at least about 1×10 5 kg / m 4 , at least about 2x10 5 kg / m 4 , at least about 3x10 5 kg / m 4 , at least about 4x10 5 kg / m 4 , at least about 5x10 5 kg / m 4 , at least about 6x10 5 kg / m 4 , at least about 7x10 5 kg / m 4 , at least about 8x10 5 kg / m 4 , at least about 9x10 5 kg / m 4 , at least about 1x10 6 kg / m 4 , at least about 2x10 6 kg / m 4 , at least about 3x106 kg / m 4 , at least about 4x10 6 kg / m 4 , at least about 5X10 6 kg / m 4 , at least about 6x10 6 kg / m 4 , at least about 7x10 6 kg / m 4 , at least about 8x10 6 kg / m 4 , at least about 9x10 6 kg / m 4 , at least about 1x10 7 kg / m 4 , at least about 2x10 7 kg / m 4 , at least about 3x10 7 kg / m 4 , at least about 4x10 7 kg / m 4 , at least about 5x10 7 kg / m 4 , at least about 6x10 7 kg / m 4 , at least about 7x10 7 kg / m 4 , at least about 8x10 7 kg / m 4 , at least about 9x10 7 kg / m 4 , at least about 1x10 8 kg / m 4 , at least about 2x10 8 kg / m 4 , at least about 3x10 8 kg / m 4 , at least about 4x10 8 kg / m 4 , at least about 5x10 8 kg / m 4 , at least about 6x10 8 kg / m 4 , at least about 7x10 8 kg / m 4 , at least about 8x10 8 kg / m 4 Or at least about 9x10 8 kg / m 4 In some embodiments, the average density gradient of cathode 230 may be no greater than about 1×10 9 kg / m 4, no larger than about 9x10 8 kg / m 4 , no larger than about 8x10 8 kg / m 4 , not larger than about 7x10 8 kg / m 4 , not larger than about 6x10 8 kg / m 4 , not larger than about 5x10 8 kg / m 4 , not larger than about 4x10 8 kg / m 4 , not more than about 3x10 8 kg / m 4 , not more than about 2x10 8 kg / m 4 , not more than about 1x10 8 kg / m 4 , no larger than about 9x10 7 kg / m 4 , no larger than about 8x10 7 kg / m 4 , not larger than about 7x10 7 kg / m 4 , not larger than about 6x10 7 kg / m 4 , not larger than about 5x10 7 kg / m 4 , not larger than about 4x10 7 kg / m 4 , not more than about 3x10 7 kg / m 4 , not more than about 2x10 7 kg / m 4 , not more than about 1x10 7 kg / m 4 , no larger than about 9x10 6 kg / m 4 , no larger than about 8x10 6 kg / m 4 , not larger than about 7x10 6 kg / m 4 , not larger than about 6x10 6 kg / m 4 , not larger than about 5x10 6 kg / m 4 , not larger than about 4x10 6 kg / m 4 , not more than about 3x10 6 kg / m 4 , not more than about 2x10 6 kg / m4 , not more than about 1x10 6 kg / m 4 , no larger than about 9x10 5 kg / m 4 , no larger than about 8x10 5 kg / m 4 , not larger than about 7x10 5 kg / m 4 , not larger than about 6x10 5 kg / m 4 , not larger than about 5x10 5 kg / m 4 , not larger than about 4x10 5 kg / m 4 , not more than about 3x10 5 kg / m 4 or no larger than approximately 2x10 5 kg / m 4 .
[0066] Combinations of the above average density gradients are also possible (e.g., at least about 1×10 s kg / m 4 and no larger than about 1x10 9 kg / m 4 Or at least about 1x10 6 kg / m 4 and no larger than about 1x10 8 kg / m 4 ), including all values and ranges therebetween. In some embodiments, the average density gradient of cathode 230 may be about 1×10 5 kg / m 4 , about 2x10 s kg / m 4 , about 3x10 5 kg / m 4 , about 4x10 5 kg / m 4 , about 5x10 s kg / m 4 , about 6x10 5 kg / m 4 , about 7x10 5 kg / m 4 , about 8x10 5 kg / m 4 , about 9x10 5 kg / m 4 , about 1x10 6 kg / m 4 , about 2x10 6 kg / m 4, about 3x10 6 kg / m 4 , about 4x10 6 kg / m 4 , about 5x10 6 kg / m 4 , about 6x10 6 kg / m 4 , about 7x10 6 kg / m 4 , about 8x10 6 kg / m 4 , about 9x10 6 kg / m 4 , about 1x10 7 kg / m 4 , about 2x10 7 kg / m 4 , about 3x10 7 kg / m 4 , about 4x10 7 kg / m 4 , about 5x10 7 kg / m 4 , about 6x10 7 kg / m 4 , about 7x10 7 kg / m 4 , about 8x10 7 kg / m 4 , about 9x10 7 kg / m 4 , about 1x10 8 kg / m 4 , about 2x10 8 kg / m 4 , about 3x10 8 kg / m 4 , about 4x10 8 kg / m 4 , about 5x10 8 kg / m 4 , about 6x10 8 kg / m 4 , about 7x10 8 kg / m 4 , about 8x10 8 kg / m 4 , about 9x10 8 kg / m 4 or about 1x10 9 kg / m 4 .
[0067] In some embodiments, the viscosity of cathode 230 (at 25° C.) can be at least about 100 Pa·s, at least about 150 Pa·s, at least about 200 Pa·s, at least about 250 Pa·s, at least about 300 Pa·s, at least about 350 Pa·s, at least about 400 Pa·s, at least about 450 Pa·s, at least about 500 Pa·s, at least about 550 Pa·s, at least about 600 Pa·s, at least about 650 Pa·s, at least about 700 Pa·s, at least about 750 Pa·s, at least about 800 Pa·s, at least about 850 Pa·s, at least about 900 Pa·s or at least about 950 Pa·s. In some embodiments, the viscosity of cathode 230 may be no greater than about 1,000 Pa·s, no greater than about 950 Pa·s, no greater than about 900 Pa·s, no greater than about 850 Pa·s, no greater than about 800 Pa·s, no greater than about 750 Pa·s, no greater than about 700 Pa·s, no greater than about 650 Pa·s, no greater than about 600 Pa·s, no greater than about 550 Pa·s, no greater than about 500 Pa·s, no greater than about 450 Pa·s, no greater than about 400 Pa·s, no greater than about 350 Pa·s, no greater than about 300 Pa·s, no greater than about 250 Pa·s, no greater than about 200 Pa·s, or no greater than about 950 Pa·s. Combinations of the above viscosities are also possible (e.g., at least about 100 Pa·s and not more than about 1,000 Pa·s or at least about 300 Pa·s and not more than about 600 Pa·s), including all values and ranges therebetween. In some embodiments, the viscosity of cathode 230 can be about 100 Pa·s, about 150 Pa·s, about 200 Pa·s, about 250 Pa·s, about 300 Pa·s, about 350 Pa·s, about 400 Pa·s, about 450 Pa·s, about 500 Pa·s, about 550 Pa·s, about 600 Pa·s, about 650 Pa·s, about 700 Pa·s, about 750 Pa·s, about 800 Pa·s, about 850 Pa·s, about 900 Pa·s, about 950 Pa·s, or about 1,000 Pa·s.
[0068] In some embodiments, cathode 230 may have a viscosity gradient. In some embodiments, a viscosity gradient may exist when electrochemical cell 200 is charged. In some embodiments, a viscosity gradient may exist when electrochemical cell 200 is discharged. In some embodiments, a viscosity gradient may exist when electrochemical cell 200 is dormant. In some embodiments, an average viscosity gradient of cathode 210 may be at least about 1×10 5 Pa·s / m, at least about 2x10 s Pa·s / m, at least about 3x10 5 Pa·s / m, at least about 4x10 5Pa·s / m, at least about 5x10 5 Pa·s / m, at least about 6x10 5 Pa·s / m, at least about 7x10 5 Pa·s / m, at least about 8x10 5 Pa·s / m, at least about 9x10 5 Pa·s / m, at least about 1x10 6 Pa·s / m, at least about 2x10 6 Pa·s / m, at least about 3x10 6 Pa·s / m, at least about 4x10 6 Pa·s / m, at least about 5x10 6 Pa·s / m, at least about 6x10 6 Pa·s / m, at least about 7x10 6 Pa·s / m, at least about 8x10 6 Pa·s / m, at least about 9x10 6 Pa·s / m, at least about 1x10 7 Pa·s / m, at least about 2x10 7 Pa·s / m, at least about 3x10 7 Pa·s / m, at least about 4x10 7 Pa·s / m, at least about 5x10 7 Pa·s / m, at least about 6x10 7 Pa·s / m, at least about 7x10 7 Pa·s / m, at least about 8x10 7 Pa·s / m, at least about 9x10 7 Pa·s / rn, at least about 1x10 8 Pa·s / m, at least about 2x10 8 Pa·s / rn, at least about 3x10 8 Pa·s / m, at least about 4x10 8 Pa·s / m, at least about 5x10 8 Pa·s / m, at least about 6x10 8 Pa·s / m, at least about 7x10 8 Pa·s / m, at least about 8x10 8 Pa·s / m or at least about 9x10 8 In some embodiments, the average viscosity gradient of cathode 210 may be no greater than about 1×10 9 Pa·s / m, not more than about 9x10 8 Pa·s / m, not more than about 8x10 8 Pa·s / m, not more than about 7x10 8Pa·s / m, not more than about 6x10 8 Pa·s / m, not more than about 5x10 8 Pa·s / m, not more than about 4x10 8 Pa·s / m, not more than about 3x10 8 Pa·s / m, not more than about 2x10 8 Pa·s / m, not more than about 1x10 8 Pa·s / m, not more than about 9x10 7 Pa·s / m, not more than about 8x10 7 Pa·s / m, not more than about 7x10 7 Pa·s / m, not more than about 6x10 7 Pa·s / m, not more than about 5x10 7 Pa·s / m, not more than about 4x10 7 Pa·s / m, not more than about 3x10 7 Pa·s / m, not more than about 2x10 7 Pa·s / m, not more than about 1x10 7 Pa·s / m, not more than about 9x10 6 Pa·s / m, not more than about 8x10 6 Pa·s / rn, not more than about 7x10 6 Pa·s / m, not more than about 6x10 6 Pa·s / m, not more than about 5x10 6 Pa·s / m, not more than about 4x10 6 Pa·s / m, not more than about 3x10 6 Pa·s / m, not more than about 2x10 6 Pa·s / m, not more than about 1x10 6 Pa·s / m, not more than about 9x10 5 Pa·s / m, not more than about 8x10 5 Pa·s / m, not more than about 7x10 s Pa·s / rn, not more than about 6x10 5 Pa·s / m, not more than about 5x10 5 Pa·s / m, not more than about 4x10 s Pa·s / m, not more than about 3x10 s Pa·s / m or not more than about 2x10 5 Pa·s / m.
[0069] Combinations of the above average viscosity gradients are also possible (e.g., at least about 1×10 5 Pa·s / m and not greater than about 1x10 9Pa·s / m or at least about 1x10 6 Pa·s / m and not greater than about 1x10 8 Pa·s / m), including all values and ranges therebetween. In some embodiments, the average viscosity gradient of cathode 230 may be about 1×10 5 Pa·s / rn, about 2x10 5 Pa·s / m, about 3x10 5 Pa·s / m, about 4x10 5 Pa·s / m, about 5x10 5 Pa·s / m, about 6x10 5 Pa·s / m, about 7x10 s Pa·s / m, about 8x10 5 Pa·s / m, about 9x10 s Pa·s / m, about 1x10 6 Pa·s / m, about 2x10 6 Pa·s / m, about 3x10 6 Pa·s / m, about 4x10 6 Pa·s / m, about 5x10 6 Pa·s / m, about 6x10 6 Pa·s / m, about 7x10 6 Pa·s / m, about 8x10 6 Pa·s / m, about 9x10 6 Pa·s / m, about 1x10 7 Pa·s / m, about 2x10 7 Pa·s / m, about 3x10 7 Pa·s / m, about 4x10 7 Pa·s / m, about 5x10 7 Pa·s / m, about 6x10 7 Pa·s / m, about 7x10 7 Pa·s / m, about 8x10 7 Pa·s / m, about 9x10 7 Pa·s / m, about 1x10 8 Pa·s / m, about 2x10 8 Pa·s / m, about 3x10 8 Pa·s / m, about 4x10 8 Pa·s / m, about 5x10 8 Pa·s / m, about 6x10 8 Pa·s / m, about 7x10 8 Pa·s / m, about 8x10 8 Pa·s / m, about 9x10 8Pa·s / m or about 1x10 9 Pa·s / m.
[0070] In some embodiments, the cathode current collector 240 may include aluminum or any other suitable current collector material. In some embodiments, the thickness of the cathode current collector 240 may be at least about 1 μm, at least about 2 μm, at least about 3 μm, at least about 4 μm, at least about 5 μm, at least about 10 μm, at least about 15 μm, at least about 20 μm, at least about 25 μm, at least about 30 μm, at least about 35 μm, at least about 40 μm, or at least about 45 μm. In some embodiments, the thickness of the cathode current collector 240 may be no greater than about 50 μm, no greater than about 45 μm, no greater than about 40 μm, no greater than about 35 μm, no greater than about 30 μm, no greater than about 25 μm, no greater than about 20 μm, no greater than about 15 μm, no greater than about 10 μm, no greater than about 5 μm, no greater than about 4 μm, no greater than about 3 μm, or no greater than about 2 μm. Combinations of the above thicknesses of the cathode current collector 240 are also possible (e.g., at least about 1 μm and not more than about 50 μm or at least about 5 μm and not more than about 20 μm), including all values and ranges therebetween. In some embodiments, the thickness of the cathode current collector 240 may be about 1 μm, about 2 μm, about 3 μm, about 4 μm, about 5 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, about 40 μm, about 45 μm, or about 50 μm.
[0071] The separator 250 may include any suitable separator that is an ion permeable membrane. In other words, the separator 250 allows ion exchange while maintaining physical separation of the cathode 230 and the anode 210. For example, the separator 250 may be any conventional membrane capable of ion transport. In some embodiments, the separator 250 is a liquid impermeable membrane that allows ion transport therethrough, i.e., a solid or gel ion conductor. In some embodiments, the separator 250 is a porous polymer membrane infused with a liquid electrolyte that allows ions to shuttle between the cathode 230 and anode 210 electroactive materials while preventing electron transfer. In some embodiments, the separator 250 may be a microporous membrane that prevents particles that form the positive and negative electrode compositions from passing through the membrane. For example, the membrane material may be selected from a polyethylene oxide (PEO) polymer or a proton conductor Nation into which a lithium salt is incorporated to provide lithium conductivity. TMMembrane. For example, a PEO-based electrolyte can be used as a membrane, which has no pinholes and is a solid ion conductor, optionally stabilized with other membranes (such as glass fiber separators) as support layers. PEO can also be used as a slurry stabilizer, dispersant, etc. in positive or negative redox compositions. PEO is stable when in contact with typical alkyl carbonate-based electrolytes. This may be particularly useful for phosphoric acid-based cell chemistries with a cell potential at a positive electrode less than about 3.6V relative to Li metal. The operating temperature of the redox cell can be increased as needed to improve the ionic conductivity of the membrane. In some embodiments, the diaphragm 250 may include polyethylene, polypropylene, polyimide, or any combination thereof.
[0072] In some embodiments, the thickness of the diaphragm 250 can be at least about 5 μm, at least about 10 μm, at least about 15 μm, at least about 20 μm, at least about 25 μm, at least about 30 μm, at least about 35 μm, at least about 40 μm, or at least about 45 μm. In some embodiments, the thickness of the diaphragm 250 can be no greater than about 50 μm, no greater than about 45 μm, no greater than about 40 μm, no greater than about 35 μm, no greater than about 30 μm, no greater than about 25 μm, no greater than about 20 μm, no greater than about 15 μm, or no greater than about 10 μm. Combinations of the above thicknesses are also possible (e.g., at least about 5 μm and no greater than about 50 μm or at least about 10 μm and no greater than about 30 μm), including all values and ranges therebetween. In some embodiments, the thickness of the membrane 250 may be about 5 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, about 40 μm, about 45 μm, or about 50 μm.
[0073] In some embodiments, the carbon coating 260 may include any of the materials listed above in connection with the carbon coating applied at step 15. In some embodiments, the carbon coating 260 may be mixed with an electrolyte solution. In some embodiments, the carbon coating 260 may be mixed with the same electrolyte solution as the anode 230. In some embodiments, the thickness of the carbon coating 260 may be at least about 500 nm, at least about 1 μm, at least about 2 μm, at least about 3 μm, at least about 4 μm, at least about 5 μm, at least about 6 μm, at least about 7 μm, at least about 8 μm, at least about 9 μm, at least about 10 μm, at least about 11 μm, at least about 12 μm, at least about 13 μm, at least about 14 μm, at least about 15 μm, at least about 16 μm, at least about 17 μm, at least about 18 μm, or at least about 19 μm. In some embodiments, the thickness of carbon coating 260 can be no greater than about 20 μm, no greater than about 19 μm, no greater than about 18 μm, no greater than about 17 μm, no greater than about 16 μm, no greater than about 15 μm, no greater than about 14 μm, no greater than about 13 μm, no greater than about 12 μm, no greater than about 11 μm, no greater than about 10 μm, no greater than about 9 μm, no greater than about 8 μm, no greater than about 7 μm, no greater than about 6 μm, no greater than about 5 μm, no greater than about 4 μm, no greater than about 3 μm, no greater than about 2 μm, or no greater than about 1 μm. Combinations of the above thicknesses of carbon coating 260 are also possible (e.g., at least about 500 nm and no greater than about 20 μm or at least about 5 μm and no greater than about 15 μm), including all values and ranges therebetween. In some embodiments, the thickness of the carbon coating 260 may be about 500 nm, about 1 μm, about 2 μm, about 3 μm, about 4 μm, about 5 μm, about 6 μm, about 7 μm, about 8 μm, about 9 μm, about 10 μm, about 11 μm, about 12 μm, about 13 μm, about 14 μm, about 15 μm, about 16 μm, about 17 μm, about 18 μm, about 19 μm, or about 20 μm.
[0074] Figure 3 3 is a schematic diagram of an electrochemical cell 300 according to an embodiment. As shown, the electrochemical cell 300 includes an anode 310 disposed on an anode current collector 320, a cathode 330 disposed on a cathode current collector 340, a separator 350 disposed between the anode 310 and the cathode 330, and a carbon coating 360 disposed between the cathode 330 and the separator 350. In some embodiments, the anode 310, the anode current collector 320, the cathode 330, the cathode current collector 340, the separator 350, and the carbon coating 360 may be the same as those described above with reference to Figure 2The anode 210, anode current collector 220, cathode 230, cathode current collector 240, separator 250, and carbon coating 260 are the same or substantially similar. Therefore, certain aspects of the anode 310, anode current collector 320, cathode 330, cathode current collector 340, separator 350, and carbon coating 360 are not described in more detail herein.
[0075] In some embodiments, the thickness of cathode 330 can be greater than the thickness of anode 310. In some embodiments, the ratio of the thickness of cathode 330 to the thickness of anode 310 can be at least about 1.1, at least about 1.2, at least about 1.3, at least about 1.4, at least about 1.5, at least about 1.6, at least about 1.7, at least about 1.8, at least about 1.9, at least about 2, at least about 2.5, at least about 3, at least about 3.5, at least about 4, at least about 4.5, at least about 5, at least about 5.5, at least about 6, at least about 6.5, at least about 7, at least about 7.5, at least about 8, at least about 8.5, at least about 9, or at least about 9.5. In some embodiments, the ratio of the thickness of cathode 330 to the thickness of anode 310 can be no greater than about 10, no greater than about 9.5, no greater than about 9, no greater than about 8.5, no greater than about 8, no greater than about 7.5, no greater than about 7, no greater than about 6.5, no greater than about 6, no greater than about 5.5, no greater than about 5, no greater than about 4.5, no greater than about 4, no greater than about 3.5, no greater than about 3, no greater than about 2.5, no greater than about 2, no greater than about 1.9, no greater than about 1.8, no greater than about 1.7, no greater than about 1.6, no greater than about 1.5, no greater than about 1.4, no greater than about 1.3, or no greater than about 1.2. Combinations of the above thickness ratios are also possible (e.g., at least about 1.1 and no greater than about 10 or at least about 3 and no greater than about 8), including all values and ranges therebetween. In some embodiments, the ratio of the thickness of the cathode 330 to the thickness of the anode 310 can be about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2, about 2.5, about 3, about 3.5, about 4, about 4.5, about 5, about 5.5, about 6, about 6.5, about 7, about 7.5, about 8, about 8.5, about 9, about 9.5, or about 10.
[0076] Figure 4A-4B A simulated graph showing the performance of an electrochemical cell. Figure 4A The cell potential at different charging times is shown when charging at 1.5 C. Fast charging of ≥ 1 C was simulated using COMSOL Multiphysics, and the electrolyte was 3.0 M, the thickness of the cathode was 190 μm, the thickness of the anode was 300 μm, and the thickness of the separator was 12 μm. Figure 4BA graph showing the salt concentration of the anode, separator, and cathode at different charging times during a 1.5C charge process is shown. As shown, the spatial coordinate of 0.0005 m corresponds to the interface between the cathode and the current collector, and the spatial coordinate of 0 m corresponds to the interface between the anode and the current collector. As shown, initially the salt concentration is uniform across the electrodes, and during the charging process of the entire electrochemical cell, the distribution of salt concentration becomes non-uniform. As shown, around 600 seconds, the average gradient of electrolyte salt concentration at t = 600 seconds is about 2x10 8 mol / m 4 , at t = 1200 seconds, it is about 2.9x10 8 mol / m 4 , and at t = 1800 seconds it is about 2.6x10 8 mol / m 4 .
[0077] Examples
[0078] Figure 5 The density of the electrolyte containing LiFSI salt in a solvent containing 3:7 (w:w) EC / DMC and 2wt% VC is shown. The x-axis represents the molar concentration of the LiFSI salt in the solution. As shown in the figure, there is a strong linear relationship between salt concentration and density. The higher the salt concentration, the greater the density.
[0079] Figure 6 The rate performance is shown for different cell orientations. The effect of gravity on rate performance was investigated in order to take advantage of density gradients in the cell. In other words, the orientation of the electrochemical cell was changed and the difference in rate performance was investigated. The data represented by the blue dots correspond to the cell being oriented vertically with the length dimension of the electrodes aligned with gravity. The data represented by the orange dots correspond to the cell being oriented horizontally with the thickness dimension of the electrodes aligned with gravity and the anode being at the top. The data represented by the green dots correspond to the cell being oriented horizontally with the cathode being at the top. As shown, the rate performance of the horizontally oriented cell is better than that of the vertically oriented cell. There is little difference between the cell with the anode at the top and the cell with the cathode at the top.
[0080] To evaluate why the horizontally oriented cells have superior rate performance, the capacity retention and area specific impedance (ASI) at 1.5C charge relative to the capacity at C / 10 charge were compared to the internal resistance (IR). Figure 7An overall negative correlation between 1.5C capacity retention and IR and a positive correlation between 1.5C capacity retention and ASI are shown. However, at similar IR values, the capacity retention of horizontally oriented cells is about 20% higher than that of vertically oriented cells. This implies the importance of cell orientation on fast charging performance. This effect is not obvious in the static state before cycling, but it becomes apparent during charging when there is a concentration gradient in the electrolyte. When the concentration gradient and gravity are in the same direction, convection caused by gravity and the density difference of the electrolyte throughout the cell can at least partially improve the fast charging performance of the cell.
[0081] Figure 8 The fast charging performance of an electrochemical cell with 2M monosalt is demonstrated. The electrolyte is formed by 2M LiFSI in EC / PC / EMC (2:1:7wt%) + 0.5wt% VC + 1.5wt% DTD + 2wt% TTE. The electrolyte is integrated into cells with 49vol% LFP and 55vol% LFP. The 49vol% LFP cell includes Ketjen black carbon, while the 55vol% LFP cell includes PBX-51. Both cells include an LFP cathode with a thickness of 200μm. The anode includes an HDL11 anode. The cell is discharged to 0.8SOC at ≥1C and charged to 1.0SOC at C / 4. The separator is a polyethylene separator. As shown in the figure, both cells retain greater than 90% of their original capacity after 100 cycles.
[0082] Fig. 9 Fast charging performance of an electrochemical cell with 2M dual salt was demonstrated. The electrolyte was formed by 1.5M LiPF6 and 0.5M LiFSI in EC / PC / EMC (2:1:7wt%) + 0.5wt% VC + 1.5wt% DTD + 2wt% TTE. The cell was discharged to 0.8SOC at ≥1C and charged to 1.0SOC at C / 4. The electrolyte was integrated into a cell with 49vol% and Ketjen black. The cell included an HDL11 anode and a polyethylene separator. As shown, the cell retained greater than 90% of its original capacity after 220 cycles.
[0083] Various concepts can be implemented as one or more methods, wherein at least one example is provided. The actions performed as part of the method can be ordered in any suitable manner. Therefore, such an embodiment can be constructed, in which the actions are performed in an order different from the order shown, which can include performing some actions simultaneously, even if the actions are shown as continuous actions in the illustrative embodiments. In other words, it should be understood that such features are not necessarily limited to a specific execution order, but can be executed in a manner consistent with the present disclosure in series, asynchronously, concurrently, in parallel, simultaneously, synchronously and / or any number of threads, processes, services, servers and / or etc. Therefore, some of these features may contradict each other because the features cannot exist in a single embodiment at the same time. Similarly, some features are applicable to an aspect of innovation and are not applicable to other aspects.
[0084] In addition, the present disclosure may include other innovations not currently described. Applicants reserve all rights to such innovations, including the right to embody such innovations, submit additional applications, continuations, partial continuations, divisions, and / or the like. Therefore, it should be understood that the advantages, embodiments, examples, functions, features, logic, operations, organizations, structures, topologies, and / or other aspects of the present disclosure should not be considered as limitations on the present disclosure as defined by the embodiments or limitations on the equivalents of the embodiments. Depending on the specific expectations and / or characteristics of individual and / or enterprise users, database configurations and / or relational models, data types, data transmission and / or network architectures, grammatical structures, and / or the like, the various embodiments of the technology disclosed herein can be implemented in a manner that implements a large amount of flexibility and customization as described herein.
[0085] All definitions, as defined and used herein, should be understood to control over dictionary definitions, definitions in documents incorporated by reference, and / or ordinary meanings of the defined terms.
[0086] As used herein, in particular embodiments, the term "about" or "approximately" when preceding a numerical value represents a range of plus or minus 10% of the value. Where a range of values is provided, it is understood that, unless the context clearly indicates otherwise, each intermediate value (to one-tenth of the unit of the lower limit) between the upper and lower limits of the range and any other stated values or intermediate values within the range are included in the present disclosure. The upper and lower limits of these smaller ranges can be independently included in smaller ranges and are also included in the present disclosure, subject to any specific exclusion limits within the range. Where the range includes one or two of the limits, the range excluding any one or two of the included limits is also included in the present disclosure.
[0087] The phrase "and / or" used herein in the specification and in the examples should be understood to mean "either or both" of the elements so combined, i.e., elements that exist jointly in some cases and separately in other cases. Multiple elements listed with "and / or" should be understood in the same way, i.e., "one or more" of the elements so combined. In addition to the elements specifically identified by the "and / or" clause, other elements may optionally be present, whether related or unrelated to those specifically identified. Therefore, as a non-limiting example, in one embodiment, when used in conjunction with open-ended language such as "comprising", references to "A and / or B" may refer only to A (optionally including elements other than B); in another embodiment, only to B (optionally including elements other than A); in yet another embodiment, to both A and B (optionally including other elements); etc.
[0088] As used herein in the specification and in the embodiments, "or" should be understood to have the same meaning as the meaning of "and / or" as defined above. For example, when the items in the list are separated, "or" or "and / or" should be interpreted as inclusive, that is, including at least one element in a plurality of elements or element lists, but also including more than one element, and optionally other unlisted items. Only explicitly pointing out the opposite term such as "only one of..." or "exactly one of..." or when used in the embodiments, "consisting of..." will refer to including exactly one element in many elements or element lists. In general, when there is an exclusive term before, such as "any one", "one of...", "only one of..." or "exactly one of...", the term "or" as used herein should only be interpreted as indicating exclusive alternatives (that is, "one or the other, not both"). When used in the embodiments, "substantially consisting of..." should have the common meaning as used in the field of patent law.
[0089] As used herein in the specification and in the examples, the phrase "at least one" with respect to a list of one or more elements should be understood to mean at least one element selected from any one or more elements in the list of elements, but does not necessarily include at least one of each element specifically listed in the list of elements, and does not exclude any combination of elements in the list of elements. This definition also allows for the optional presence of elements in addition to the elements specifically identified in the list of elements to which the phrase "at least one" refers, whether related to or unrelated to the specifically identified elements. Thus, as a non-limiting example, in one embodiment, "at least one of A and B" (or equivalently, "at least one of A or B", or equivalently "at least one of A and / or B") may refer to at least one that optionally includes more than one A, does not have B (and optionally includes elements other than B); in another embodiment, may refer to at least one that optionally includes more than one B, does not have A (and optionally includes elements other than A); in yet another embodiment, may refer to at least one that optionally includes more than one A, and optionally includes more than one B (and optionally includes other elements); etc.
[0090] In the examples and in the above description, all transitional phrases such as "comprising", "including", "carrying", "having", "containing", "involving", "holding", "comprising", etc. should be understood as open-ended, i.e., meaning including but not limited to. As described in Section 2111.03 of the Manual of Patent Examining Procedures of the United States Patent Office, only the transitional phrases "consisting of" and "consisting essentially of" should be closed or semi-closed transitional phrases, respectively.
[0091] Although specific embodiments of the present disclosure have been summarized above, many substitutions, modifications and variations are apparent to those skilled in the art. Therefore, the embodiments set forth herein are intended to be illustrative rather than restrictive. Various changes may be made without departing from the spirit and scope of the present disclosure. Where the above methods and steps indicate specific events occurring in a particular order, those of ordinary skill in the art who benefit from the present disclosure will recognize that the order of specific steps may be modified, and such modifications are variations according to the present invention. In addition, as described above, certain steps in the steps may be performed simultaneously in a parallel process, as well as sequentially, where possible. Embodiments have been specifically shown and described, but it will be appreciated that various changes in form and detail may be made.
Claims
1. An electrochemical cell comprising: cathode current collector; a semi-solid cathode disposed on the cathode current collector, the semi-solid cathode having a thickness of at least about 150 μm, and comprising an active material, a conductive material, and an electrolyte, the electrolyte comprising a non-aqueous solvent and an electrolyte salt; Anode current collector; an anode, the anode being disposed on the anode current collector; as well as a separator disposed between the anode and the cathode, The average concentration gradient of the electrolyte salt in the semi-solid cathode is at least about 2×10 7 mol / m 4 .
2. The electrochemical cell of claim 1, wherein the average concentration of the electrolyte salt in the non-aqueous liquid electrolyte is at least about 2,000 mol / m 3 .
3. The electrochemical cell of claim 2, wherein the average concentration of the electrolyte salt in the non-aqueous liquid electrolyte is at least about 3,000 mol / m 3 .
4. The electrochemical cell of claim 1, wherein the average concentration gradient of the electrolyte salt in the semi-solid cathode is at least about 3 x 10 7 mol / m 4 .
5. The electrochemical cell of claim 1, wherein the electrolyte salt comprises at least one of lithium bis(oxalato)borate (LiBOB), lithium hexafluorophosphate (LiPF6), or lithium bis(fluorosulfonyl)imide (LiFSI).
6. The electrochemical cell of claim 1, wherein the separator is coated with a non-aqueous liquid electrolyte.
7. The electrochemical cell of claim 6, wherein the separator is coated with hard carbon.
8. A method comprising: The active material is combined with a conductive material and a non-aqueous liquid electrolyte having a salt concentration of at least about 2,000 mol / m 3 ; disposing the semi-solid cathode onto a cathode current collector, the semi-solid cathode having a thickness of at least about 150 μm; placing the anode on the anode current collector; wetting the first surface of the separator with the nonaqueous liquid electrolyte; coating the first surface of the diaphragm with a carbon coating; as well as The anode is positioned on the cathode with the separator interposed therebetween to form an electrochemical cell such that the first surface of the separator is in contact with the semi-solid cathode.
9. The method according to claim 8, further comprising: The electrochemical cell is charged and discharged while orienting the electrochemical cell such that the thickness of the cathode is aligned with the direction of gravity.
10. The method of claim 8, wherein the salt concentration of the non-aqueous liquid electrolyte is at least about 3,000 mol / m 3 .
11. The method of claim 8, wherein the carbon coating comprises hard carbon.
12. The method of claim 9, wherein the rate of said charging and said discharging is at least about 1.5C.
13. The method of claim 8, further comprising: The electrochemical cell is charged and discharged while at least one of a magnetic field, heat, or centrifugal force is applied to the electrochemical cell.
14. The method according to claim 8, wherein the first non-aqueous liquid electrolyte comprises at least one of vinylene carbonate (VC), 1,3-propane sultone (PS), ethyl propionate (EP), 1,3-propylene glycol cyclic sulfate (PSA / TS), fluoroethylene carbonate (FEC), ethylene sulfite (ES), tri(2-ethylhexyl) phosphate (TOP), ethylene sulfate (DTD), ethyl acetate (EA), maleic anhydride (MA), ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC) or ethyl methyl carbonate (EMC).
15. An electrochemical cell comprising: First Collector Fluid; a first electrode material disposed on the first current collector and having a semi-solid composition, the first electrode material having a thickness of at least about 150 μm, and the first electrode material comprising an active material, a conductive material, an electrolyte salt, and an electrolyte solvent, the electrolyte salt having a concentration gradient of at least about 2×10 7 mol / m 4 ; Second episode fluid; a second electrode material, the second electrode material being disposed on the second current collector; a separator disposed between the first electrode material and the second electrode material; as well as A carbon coating is disposed between the first electrode material and the separator.
16. The electrochemical cell of claim 15, wherein the carbon coating comprises at least one of hard carbon, disordered carbon, graphite, graphitic or non-graphitic carbon, amorphous carbon, mesocarbon, microbeads, soft carbon, activated carbon, or a graphitic-hard carbon mixture.
17. The electrochemical cell of claim 15, wherein the electrolyte solvent is a non-aqueous solvent.
18. The electrochemical cell of claim 15, wherein the concentration gradient of the electrolyte salt along the thickness of the first electrode material is at least about 3 x 10 7 mol / m 4 .
19. The electrochemical cell of claim 15, wherein the electrolyte salt comprises at least one of lithium bis(oxalato)borate (LiBOB), lithium hexafluorophosphate (LiPF6), or lithium bis(fluorosulfonyl)imide (LiFSI).
20. The electrochemical cell of claim 15, wherein the viscosity gradient of the first electrode is at least about 5 x 10 5 Pa.s / m.